One-component (1K) curable adhesive composition

By developing a curable and electrochemically defragable single component (1K) adhesive composition, the problem of difficult disassembly and inability to reuse existing adhesives is solved, and efficient disassembly and reuse of adhesives is achieved.

CN119790090APending Publication Date: 2025-04-08HENKEL KGAA
View PDF 36 Cites 0 Cited by

Patent Information

Application Number
CN202380062916.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-05
Filing Date
2023-08-15
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

Existing adhesives are difficult to remove when they need to be disassembled, and the cured chemical network cannot be used as an adhesive in most cases, limiting the recycling and reuse of resources.

Method used

A curable and electrochemically debonable single component (1K) adhesive composition is developed, which comprises an epoxy compound, a curing agent, a repairing agent and an electrolyte, which after the electrochemical debonding operation allows the adhesive to be used again to form the composite structure.

Benefits of technology

It is realized that the adhesive can effectively bond the substrate after curing, and after the electrochemical debonding operation, the adhesive can be used for the bonding of the substrate again, which improves the possibility of resource recycling and reuse.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005290982700000071
    Figure BDA0005290982700000071
  • Figure BDA0005290982700000081
    Figure BDA0005290982700000081
  • Figure BDA0005290982700000131
    Figure BDA0005290982700000131
Patent Text Reader

Abstract

The present disclosure relates to a curable and electrochemically debondable one-component (1K) adhesive composition comprising: a) at least one epoxy compound; b) a curing agent consisting of one or more compounds having at least one epoxy-reactive group and not having a disulfide functional group; c) a repair agent consisting of one or more compounds containing at least one disulfide functional group and optionally at least one epoxy reactive group selected from the group consisting of hydroxyl, thiol, amine, or carboxyl; and d) an electrolyte, wherein the composition is characterized by a molar ratio of epoxy reactive groups to epoxy groups of from 0.6: 1 to 1.2: 1.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a one-component (1K) curable adhesive composition which, after curing, can bond substrates together and can withstand loads within a bonded composite structure, but which can also be electrochemically debonded from a particular substrate to which it is applied. More specifically, the present invention relates to a one-component (1K) curable and electrochemically debondable adhesive composition which, after an electrochemical debonding operation, at least partially recovers its ability to bond substrates and withstand loads within a bonded composite structure. Background Art

[0002] Adhesive bonding and polymer coatings are commonly used in the assembly and finishing of manufactured products. They are used to replace mechanical fasteners such as screws, bolts, and rivets to provide bonding at reduced machine costs and greater applicability in the manufacturing process. Adhesive bonding distributes stress evenly, reduces the potential for fatigue, and seals joints from corrosive substances.

[0003] Although adhesive bonding thus offers many advantages over mechanical fasteners, certain disadvantages must also be acknowledged. Firstly, in practical applications, it tends to be difficult to disassemble adhesively bonded articles when this is desired. Secondly, when the adhesive has cured in situ to bond two substrates together, a cross-linked chemical network is formed: after disassembly of the adhesively bonded articles, this chemical network cannot in most cases be used again as an adhesive. These disadvantages have been particularly concentrated in those industries that are usually resource-intensive and in which it would be beneficial to recycle, reuse or recycle the manufactured products.

[0004] With respect to the first identified disadvantage, adhesive removal by mechanical methods (such as by sandblasting or by wire brushing) is generally precluded, in part because the adhesive is disposed between the substrates and is therefore difficult to access or to abrade without damaging the substrate surfaces. Disassembly by application of chemicals and / or elevated temperatures (as disclosed in U.S. Pat. No. 4,171,240 (Wong), U.S. Pat. No. 4,729,797 (Linde et al.), and US20140287299 A1 (Krogdahl)) may be effective, but can be time-consuming and complicated to perform; particularly if it is desired to retain the substrate surfaces having residual adhesive disposed thereon: the aggressive chemicals and / or harsh conditions required typically remove substantially all of the adhesive and damage the separated substrates, rendering them unsuitable for subsequent applications.

[0005] As an exemplary case, it is clearly desirable to remove, replace and / or recycle components of electronic devices (such as laptop computers and phones) that have been attached within the device using adhesives. However, such adhesives are generally robust because they are designed to maintain adhesion during drops or shock events and over a wide range of operating temperatures and other environmental conditions. If care is not taken, adhesive-bonded device components may be damaged or destroyed when the components are removed by mechanical means, application of chemicals or high temperatures.

[0006] With these problems in mind, some authors have attempted to develop debondable adhesive compositions in which an electric current is passed through the cured composition to break the bond at the interface of the adhesive with the substrate.

[0007] U.S. Pat. No. 7,465,492 (Gilbert) describes a debondable composition comprising: a matrix functional group comprising a monomer selected from the group consisting of acrylics, methacrylics, and combinations thereof; a free radical initiator; and an electrolyte, wherein the electrolyte provides sufficient ionic conductivity to the composition to support a faradaic reaction at a bond formed between the composition and a conductive surface and thereby debond the composition from the surface.

[0008] US2007 / 0269659 (Gilbert) describes an adhesive composition that is debondable at two interfaces, which composition: (i) comprises a polymer and an electrolyte; (ii) promotes bonding of the two surfaces; and (iii) responds to a voltage applied across the two surfaces to form an anodic interface and a cathodic interface, thereby debonding from both the anodic surface and the cathodic surface.

[0009] US2008 / 0196828 (Gilbert) describes a hot melt adhesive composition comprising: a thermoplastic component; and an electrolyte, wherein the electrolyte provides sufficient ionic conductivity to the composition to effect a Faradaic reaction at a bond formed between the composition and a conductive surface and to debond the composition from the surface.

[0010] WO2017 / 133864 (Henkel AG & Co. KGaA) describes a method for reversibly bonding a first substrate and a second substrate, wherein at least the first substrate is a non-conductive substrate, the method comprising: a) coating the surface of one or more non-conductive substrates with a conductive ink; b) applying an electrically debondable hot melt adhesive composition to the surface of the first substrate coated with the conductive ink and / or the second substrate; c) contacting the first substrate with the second substrate so that the electrically debondable hot melt adhesive composition is sandwiched between the two substrates; d) forming an adhesive bond between the two substrates to provide a bonded substrate; and e) applying a voltage to the bonded substrates, whereby the adhesion at at least one interface between the electrically debondable hot melt adhesive composition and the substrate surface is substantially weakened.

[0011] WO2021 / 115771A1 (Henkel AG & Co. KGaA) relates to a curable and debondable one-component (1K) adhesive composition comprising: a) an epoxy resin; b) a curing agent for the epoxy resin; c) an electrolyte; and d) a non-conductive filler; wherein the composition comprises at least one of: e) a combination of a solubilizer and a toughening agent; and f) conductive particles.

[0012] Despite the advantageous development of electrochemically debondable adhesive compositions, none of the above citations provide for the reuse of debonded adhesives in forming composite structures. It is therefore believed that there is still a need in the art to provide adhesive compositions that can be conveniently applied to the surfaces of substrates to be bonded; that, after curing, can provide effective bonding within composite structures containing said substrates; that can be effectively debonded from those substrates by easily applying an electrical potential across the cured adhesive; but that can also allow the cured adhesive to be reused for effective bonding of substrates. Such debondable adhesives have advantageous utility, particularly in electronic devices. Summary of the invention

[0013] According to a first aspect of the present invention, there is provided a curable and electrochemically debondable one-component (1K) adhesive composition, the composition comprising:

[0014] a) at least one epoxy compound;

[0015] b) a curing agent, the curing agent consisting of one or more compounds having at least one epoxide reactive group and no disulfide functional group;

[0016] c) a healing agent consisting of one or more compounds containing at least one disulfide functional group and optionally at least one epoxy reactive group selected from hydroxyl, thiol, amine, or carboxyl; and

[0017] d) electrolytes,

[0018] The composition is characterized in that the molar ratio of epoxy-reactive groups to epoxy groups is from 0.6:1 to 1.2:1.

[0019] In an important embodiment of the present invention, the composition comprises, based on the weight of the composition:

[0020] 15 to 50 wt. %, preferably 20 to 50 wt. %, more preferably 20 to 40 wt. % of a) at least one polyepoxide;

[0021] 0.01 to 25% by weight, preferably 5 to 25% by weight, more preferably 5 to 20% by weight of b) a curing agent consisting of one or more compounds having at least two epoxy-reactive groups and no disulfide functionality;

[0022] 0.01 to 10 wt %, preferably 1 to 10 wt %, more preferably 2 to 8 wt % of c) the repair agent;

[0023] 0.5 to 15 wt %, preferably 0.5 to 10 wt %, more preferably 0.5 to 5 wt % of d) the electrolyte; and

[0024] 0 to 55 wt. %, preferably 1 to 55 wt. %, more preferably 15 to 55 wt. % of e) a rheology control agent,

[0025] The composition is characterized in that the molar ratio of epoxy reactive groups to epoxy groups is 0.6:1 to 1.1:1, preferably 0.75:1 to 1:1, more preferably 0.75:1 to 0.95:1. Preferably, the polyepoxide of the composition is selected from bisphenol A epoxy resin, bisphenol F epoxy resin, and mixtures thereof.

[0026] Compositions according to these definitions have been demonstrated to provide excellent bond stability, even under conditions of high temperature and humidity: the examples below demonstrate stability, in particular at 95% relative humidity (RH) and 65° C. Furthermore, when composite structures have been formed using the cured adhesive compositions, these structures are easily debonded by applying a potential difference across the adhesive bonds.

[0027] The presence of the repair agent allows the cured composition of the present disclosure to be used again to form a bonded structure after the initial composite structure has been subjected to an electrochemical debonding operation. Under thermal activation, disulfide rearrangement is believed to occur within the cured matrix: the resulting change in the matrix topology of the previously cured and debonded adhesive allows the adhesive to bond the substrates together. The following examples demonstrate a significant recovery of the bond strength after thermal activation relative to the bond strength of the initial cured adhesive composition.

[0028] Preferably, the curing agent in b) of the composition comprises or consists of a thiol-functional compound selected from pentaerythritol tetrakisthioacetate (PETMP), tris(3-mercaptopropionate) (TMP), trimethylolpropane trimercaptoacetate (TMPMP), tris(2-(mercaptopropionyl)ethyl)isocyanate, ethylene glycol dimercaptoacetate, and mixtures thereof.

[0029] In an embodiment, the repair agent comprises a compound selected from the group consisting of: bis(4-aminophenyl) disulfide; bis(2-aminophenyl) disulfide; 2-amino-4-chlorophenyl disulfide; and mixtures thereof. In an alternative embodiment, the repair agent comprises a compound selected from the group consisting of: 3,3'-dithiopropionic acid; 4,4'-dithiobutyric acid; bis(10-carboxydecyl) disulfide; 2,2'-dithiobisethylamine (cystamine); (2R)-2-amino-3-[[(2R)-2-amino-2-carboxyethyl]disulfanyl]propanoic acid (L-cystine); and mixtures thereof. In another alternative embodiment, the repair agent comprises a liquid thiol-terminated polysulfide polymer.

[0030] Independently or additionally to this preferred statement for the curing agent and the healing agent, preferably, the electrolyte is selected from: 1-ethyl-3-methyl-1H-imidazol-3-ium methane sulfonate; 1-ethyl-3-methyl-1H-imidazol-3-ium methyl sulfate; 1-methylimidazolium bis(trifluoromethylsulfonyl)imide; 3-methylimidazolium bis(trifluoromethylsulfonyl)imide; 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide; 1-propyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide; 1-butyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide; 1-butyl-2,3-dimethylimidazolium bis(trifluoromethylsulfonyl)imide; 1-hexyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide; amine; 1-octyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide; 1-methyl-3-octylimidazolium bis(trifluoromethylsulfonyl)imide; 1-decyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide; 1-dodecyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide; tetraethylphosphonium bis(trifluoromethylsulfonyl)imide; tetrabutylphosphonium Phosphonium bis(trifluoromethylsulfonyl)imide; Tetraoctylphosphonium bis(trifluoromethylsulfonyl)imide; Trihexyl(tetradecyl)phosphonium bis(trifluoromethylsulfonyl)imide; Tridecyl(tetradecyl)phosphonium bis(trifluoromethylsulfonyl)imide; Tributyl(methyl)phosphonium diethyl phosphate; Tributyl(ethyl)phosphonium diethyl phosphate; Tetraoctylphosphonium diethyl phosphate; and mixtures thereof. It may be noted that the electrolyte is particularly preferably selected from: 1-ethyl-3-methyl-1H-imidazol-3-ium methanesulfonate; 1-ethyl-3-methyl-1H-imidazol-3-ium methylsulfate; Trihexyl(tetradecyl)phosphonium bis(trifluoromethylsulfonyl)imide; Tributyl(methyl)phosphonium diethyl phosphate; Tributyl(ethyl)phosphonium diethyl phosphate; and mixtures thereof.

[0031] According to a second aspect of the present invention, there is provided a bonded structure comprising:

[0032] a first substrate having a conductive surface; and

[0033] a second substrate having a conductive surface;

[0034] wherein a cured adhesive composition as defined above and in the appended claims is disposed between the first substrate and the second substrate.

[0035] The present disclosure also provides for the use of a cured composition as defined above and in the appended claims as an adhesive. Prior to using the previously cured composition in this manner, the cured composition is heat treated to activate disulfide bond re-arrangement therein.

[0036] According to another aspect of the present invention, there is provided a method of forming and re-forming a bonded structure, the method comprising the steps of:

[0037] A first bonded structure is provided, the first bonded structure comprising:

[0038] a first substrate having a conductive surface;

[0039] a second substrate having a conductive surface; and

[0040] a cured adhesive composition as defined above and in the appended claims disposed between the first substrate and the second substrate;

[0041] applying a voltage across two conductive surfaces to form an anodic interface and a cathodic interface;

[0042] debonding the first substrate and the second substrate;

[0043] contacting the debonded first substrate with a third substrate so that the cured adhesive composition is sandwiched between the first substrate and the third substrate; and

[0044] The residual cured adhesive composition is heat treated to bond the first substrate and the third substrate together.

[0045] definition

[0046] As used herein, the singular forms "a", "an", and "the" include plural referents unless the context clearly dictates otherwise.

[0047] As used herein, the terms "comprising / comprises / comprised of" are synonymous with "including / includes" or "containing / contains", are inclusive or open-ended, and do not exclude additional unrecited members, elements, or method steps.

[0048] As used herein, the term "consisting of excludes any elements, ingredients, members, or method steps not specified.

[0049] When amounts, concentrations, sizes and other parameters are expressed in the form of ranges, preferred ranges, upper values, lower values, or preferred upper and lower values, it should be understood that any range obtainable by combining any upper value or preferred value with any lower value or preferred value is also specifically disclosed, regardless of whether the obtained range is explicitly mentioned in the context.

[0050] Furthermore, according to standard understanding, weight ranges expressed as "0-x / 0 to x" specifically include 0 wt %: the ingredient defined by the range may not be present in the composition or may be present in the composition in an amount of up to x wt %.

[0051] The words "preferred / preferably", "desirable", and "particularly / especially" are generally used herein to refer to embodiments of the present disclosure that may provide particular benefits in certain circumstances. However, the recitation of one or more preferred, preferred, desirable, or particular embodiments does not mean that other embodiments are not useful, and is not intended to exclude those other embodiments from the scope of the present disclosure.

[0052] The word "exemplary" is used herein to mean serving as an example, instance, or illustration. Any aspect or design described herein as "exemplary" is not necessarily to be construed as preferred or advantageous over other aspects or designs. On the contrary, the use of the word exemplary is intended to present concepts in a concrete manner.

[0053] As used throughout this application, the words "may" are used in a permissive sense (ie, meaning having the potential to), rather than in a mandatory sense.

[0054] As used herein, room temperature is 23° C.±2° C. As used herein, “ambient conditions” means the temperature and pressure of the environment to which a composition is exposed or to which a coating or substrate of the coating is exposed.

[0055] As used herein, the term "debondable" means that after the adhesive is cured, the bond strength can be weakened by at least 50% after applying a potential of 0.5V to 100V for a duration of 1 second to 60 minutes. The cured adhesive is applied between two substrates bonded by the adhesive so that an electric current flows through the adhesive bonding layer. The bond strength is measured by a tensile lap shear (TLS) test performed at room temperature based on EN1465:2009 (German version) based on the determination of tensile lap shear strength of adhesive-bonded assemblies.

[0056] As used herein, the term "monomer" refers to a substance that can undergo a polymerization reaction to provide a building block for the chemical structure of a polymer. As used herein, the term "monofunctional" refers to having one polymerizable moiety. As used herein, the term "multifunctional" refers to having more than one polymerizable moiety.

[0057] As used herein, the term "equivalent" (eq.) refers, as usual in chemical notation, to the relative quantity of reactive groups present in a reaction.

[0058] The term "electrolyte" is used herein according to its standard meaning in the art as a substance containing free ions that can conduct electricity by displacement of charge carrier species. The term is intended to encompass molten electrolytes, liquid electrolytes, semisolid electrolytes, and solid electrolytes in which at least one of the cationic or anionic components of the electrolyte structure is substantially free to displace, thereby acting as a charge carrier.

[0059] The curable adhesive composition of the present invention and the cured adhesive obtained therefrom have "electrolyte function" because the adhesive material allows the conduction of ions (anions, cations, or both anions and cations). The electrolyte function is understood to be derived from the ability of the composition and the cured adhesive to solvate ions of at least one polarity.

[0060] As used herein, "(meth)acryl" is a shorthand term for "acryl" and / or "methacryl." Thus, the term "(meth)acrylamide" refers collectively to acrylamide and methacrylamide.

[0061] As used herein, “C1-C n An "alkyl" group refers to a monovalent group containing 1 to n carbon atoms, which is a radical of an alkane and includes straight-chain and branched organic groups. Thus, a "C1-C 18 An "alkyl" group refers to a monovalent group containing 1 to 18 carbon atoms, which is a radical of an alkane and includes straight-chain and branched organic groups. In general, it should be noted that alkyl groups (C1-C 12 Alkyl) such as alkyl containing 1-8 carbon atoms (C1-C8 alkyl). Examples of alkyl include, but are not limited to, methyl; ethyl; propyl; isopropyl; n-butyl; isobutyl; sec-butyl; tert-butyl; n-pentyl; n-hexyl; n-heptyl; and 2-ethylhexyl. In the present invention, such alkyl groups may be unsubstituted or may be substituted with one or more halogens. When applicable to a given portion (R), the specification will indicate the tolerance for one or more non-halogen substituents in the alkyl group.

[0062] As used herein, the term "C1-C 18 "Hydroxyalkyl" refers to a HO-(alkyl) group having 1-18 carbon atoms, wherein the point of attachment of the substituent is through the oxygen atom and alkyl is as defined above.

[0063] "Alkoxy" refers to a monovalent group represented by -OA, where A is an alkyl group: non-limiting examples of which are methoxy, ethoxy, and isopropoxy. As used herein, the term "C1-C 18 "Alkoxyalkyl" refers to an alkyl group having an alkoxy substituent as defined above, and wherein the moiety (alkyl-O-alkyl) contains 1 to 18 carbon atoms in total: such groups include methoxymethyl (-CH2OCH3), 2-methoxyethyl (-CH2CH2OCH3) and 2-ethoxyethyl. Similarly, as used herein, the term "C7-C 18 "Alkoxyaryl" refers to an aryl group having an alkoxy substituent as defined above and wherein the moiety (aryl-O-alkyl) has 7 to 18 carbon atoms in total.

[0064] As used herein, the term "C2-C4 alkylene" is defined as a saturated divalent hydrocarbon group having 2 to 4 carbon atoms.

[0065] The term "C3-C 18 "Cycloalkyl" should be understood to mean a saturated monocyclic or polycyclic hydrocarbon radical having 3 to 18 carbon atoms. In the present invention, such cycloalkyl groups may be unsubstituted or may be substituted by one or more halogens. When applicable to a given moiety (R), the specification will indicate the tolerance for one or more non-halogen substituents in the cycloalkyl group. Examples of cycloalkyl groups include: cyclopropyl; cyclobutyl; cyclopentyl; cyclohexyl; cycloheptyl; cyclooctyl; adamantane; and norbornane.

[0066] As used herein, "C6-C8" used alone or as part of a larger moiety (such as in "aralkyl") 18 "Aryl" groups refer to monocyclic, bicyclic and tricyclic ring systems, wherein the monocyclic ring system is aromatic or at least one of the rings in the bicyclic or tricyclic ring system is aromatic. Bicyclic and tricyclic ring systems include benzo-fused 2-3 membered carbon rings. In the present invention, such aryl groups may be unsubstituted or may be substituted with one or more halogens. When applicable to a given portion (R), the specification will indicate the tolerance for one or more non-halogen substituents in the aryl group. Exemplary aryl groups include: phenyl; (C1-C4) alkylphenyls, such as tolyl and ethylphenyl; indenyl; naphthyl, tetrahydronaphthyl, tetrahydroindenyl; tetrahydroanthracenyl; and anthracenyl. In addition, it can be noted that phenyl is preferred.

[0067] As used herein, “C2-C 20"Alkenyl" refers to a hydrocarbon group having 2-20 carbon atoms and at least one ethylenically unsaturated unit. The alkenyl group may be linear, branched or cyclic, and may be optionally substituted with one or more halogens. When applicable to a given portion (R), the specification will indicate the tolerance of one or more non-halogen substituents in the alkenyl group. As understood by those of ordinary skill in the art, the term "alkenyl" also includes groups having "cis" and "trans" configurations, or alternatively "E" and "Z" configurations. However, in general, it should be noted that alkenyl groups containing 2-10 carbon atoms (C 2-10 ) or contains 2-8 carbon atoms (C 2-8 ) is an unsubstituted alkenyl. 12 Examples of alkenyl groups include, but are not limited to: —CH═CH2; —CH═CHCH3; —CH2CH═CH2; —C(═CH2)(CH3); —CH═CHCH2CH3; —CH2CH═CHCH3; —CH2CH2CH═CH2; —CH═C(CH3)2; —CH2C(═CH2)(CH3); —C(═CH2)CH2CH3; —C(CH3)═CHCH3; —C(CH3)CH═CH2; —CH═CHCH2CH2CH3; —CH2CH ═CHCH2CH3; —CH2CH2CH═CHCH3; —CH2CH2CH2CH═CH2; —C(═CH2)CH2CH2CH3; —C(CH3)═CHCH2CH3; —CH(CH3)CH═CHCH; —CH(CH3)CH2CH═CH2; —CH2CH═C(CH3)2; 1-cyclopent-1-enyl; 1-cyclopent-2-enyl; 1-cyclopent-3-enyl; 1-cyclohex-1-enyl; 1-cyclohex-2-enyl; and 1-cyclohexyl-3-enyl.

[0068] As used herein, "alkylaryl" refers to an aryl group substituted by an alkyl group, both groups being as defined above. Additionally, as used herein, "aralkyl" means an alkyl group substituted by an aryl group as defined above.

[0069] As used herein, the term "hetero" refers to a group or moiety that contains one or more heteroatoms such as N, O, Si and S. Thus, for example, "heterocycle" refers to a cyclic group having, for example, N, O, Si or S as part of the ring structure. "Heteroalkyl", "heterocycloalkyl" and "heteroaryl" moieties are alkyl, cycloalkyl and aryl groups, respectively, as defined above, containing N, O, Si or S as part of their structure.

[0070] As used herein, the term "equivalent weight" refers to the molecular weight divided by the number of functional groups involved. Thus, "epoxy equivalent weight" (EEW) means the weight (in grams) of a resin containing one equivalent of epoxy groups.

[0071] As used herein, the term "epoxide" means a compound characterized by the presence of at least one cyclic ether group, i.e., a compound in which an ether oxygen atom is connected to two adjacent carbon atoms to form a cyclic structure. The term is intended to include monoepoxides, polyepoxides (having two or more epoxy groups), and epoxy-terminated prepolymers. The term "monoepoxide" is intended to mean an epoxy compound having one epoxy group. The term "polyepoxide" is intended to mean an epoxy compound having at least two epoxy groups. The term "diepoxide" is intended to mean an epoxy compound having two epoxy groups.

[0072] The epoxy compound may be unsubstituted, but may also be inertly substituted. Exemplary inert substituents include chlorine, bromine, fluorine and phenyl.

[0073] As used herein, the term "disulfide group" refers to a functional group having the structure RSS-R'. When a compound is referred to as a disulfide, the compound must have a -SS- bond.

[0074] Molecular weights referred to in this specification may be measured using gel permeation chromatography (GPC) using polystyrene calibration standards, such as performed according to ASTM 3536.

[0075] As used herein, the term softening point (° C.) used herein with respect to waxes is the ring and ball softening point, which is measured according to ASTM E28 unless otherwise indicated.

[0076] Unless otherwise specified, the viscosity of the compositions described herein is measured using an Anton Paar viscometer (model MCR 301) at standard conditions of 25°C and 50% relative humidity (RH). The viscometer is calibrated once a year and checked by the service department. Calibration uses known viscosities ranging from 1 cps to 50,000 cps (parallel plate PP20, shear rate 1 s -1 The composition according to the invention is measured using a parallel plate PP20 at 1.5 to 100 s -1 was carried out at different shear rates. DETAILED DESCRIPTION

[0077] a) Epoxy compounds

[0078] The composition of the present disclosure necessarily comprises at least one epoxy compound. Typically, the composition comprises 15 to 50 wt. % of a) the at least one epoxy compound, based on the weight of the composition: preferably, the total amount of one or more epoxy compounds is 20 to 50 wt. %, such as 20 to 40 wt. % of the composition.

[0079] Epoxides used herein can include monofunctional epoxides, multifunctional epoxides (multi-or poly-functional epoxide compounds), and combinations thereof. Component a) of the composition can consist of a single epoxide, but can also be a mixture of epoxide-functional compounds, including mixtures of compounds having different numbers of epoxide groups per molecule. Epoxides can be saturated or unsaturated, aliphatic, alicyclic, aromatic or heterocyclic, and can be substituted. In addition, epoxides can be monomeric or polymeric.

[0080] Without intending to limit the present invention, exemplary monoepoxides include: alkylene oxides; epoxy-substituted alicyclic hydrocarbons, such as cyclohexene oxide, vinylcyclohexene monooxide, (+)-cis-limonene oxide, (+)-cis,trans-limonene oxide, (-)-cis,trans-limonene oxide, cyclooctene oxide, cyclododecene oxide, and α-pinene oxide; epoxy-substituted aromatic hydrocarbons; monoepoxy-substituted alkyl ethers of monohydric alcohols or phenols, such as glycidyls of aliphatic, alicyclic and aromatic alcohols; ethers; monoepoxy-substituted alkyl esters of monocarboxylic acids, such as glycidyl esters of aliphatic, cycloaliphatic and aromatic monocarboxylic acids; monoepoxy-substituted alkyl esters of polycarboxylic acids, in which one or more other carboxyl groups are esterified with alkanols; alkyl and alkenyl esters of epoxy-substituted monocarboxylic acids; epoxy alkyl ethers of polyols, in which one or more other OH groups are esterified or etherified with carboxylic acids or alcohols; and monoesters of polyols and epoxy monocarboxylic acids, in which one or more other OH groups are esterified or etherified with carboxylic acids or alcohols.

[0081] For example, the following glycidyl ethers can be mentioned as particularly suitable monoepoxide compounds for use herein: methyl glycidyl ether; ethyl glycidyl ether; propyl glycidyl ether; butyl glycidyl ether; pentyl glycidyl ether; hexyl glycidyl ether; cyclohexyl glycidyl ether; octyl glycidyl ether; 2-ethylhexyl glycidyl ether; allyl glycidyl ether; benzyl glycidyl ether; phenyl glycidyl ether; 4-tert-butylphenyl glycidyl ether; 1-naphthyl glycidyl ether; 2-naphthyl glycidyl ether; 2-chlorophenyl glycidyl ether; 4-chlorophenyl glycidyl ether; 4-bromophenyl glycidyl ether; 2,4,6-trichlorophenyl glycidyl ether; 2,4,6-tribromophenyl glycidyl ether; pentafluorophenyl glycidyl ether; o-cresyl glycidyl ether; m-cresyl glycidyl ether; and p-cresyl glycidyl ether.

[0082] In an embodiment, the monoepoxide conforms to the following formula (E):

[0083]

[0084] Where: R w , R x , R y and R z may be the same or different and are independently selected from hydrogen, halogen atoms, C1-C8 alkyl, C3-C 10 Cycloalkyl, C2-C 12 Alkenyl, C6-C 18 Aryl, or C7-C 18 Aralkyl, provided that R y and R z At least one of is not hydrogen.

[0085] Preferably, R w , R x and R y is hydrogen, and R z It is phenyl or C1-C8 alkyl, more preferably C1-C4 alkyl.

[0086] With regard to this embodiment, exemplary monoepoxides include: ethylene oxide; 1,2-propylene oxide (propylene oxide); 1,2-butylene oxide; cis-2,3-butylene oxide; trans-2,3-butylene oxide; 1,2-pentene oxide; 1,2-hexene oxide; 1,2-heptane oxide; decane oxide; butadiene oxide; isoprene oxide; and styrene oxide.

[0087] In the present invention, it is mentioned to use at least one monoepoxide compound selected from the group consisting of ethylene oxide; propylene oxide; cyclohexene oxide; (+)-cis-limonene oxide; (+)-cis,trans-limonene oxide; (-)-cis,trans-limonene oxide; cyclooctene oxide; and cyclododecene oxide.

[0088] Again, without intending to limit the invention, suitable polyepoxides may be liquids, solids, or solutions in solvents. Additionally, such polyepoxides should have an epoxy equivalent weight of 100 to 700 g / equivalent, such as 120 to 320 g / equivalent. Additionally, typically, diepoxides having an epoxy equivalent weight of less than 500 g / equivalent or even less than 400 g / equivalent are preferred: this is primarily from a cost perspective, since lower molecular weight epoxy resins require more limited processing in purification in their production.

[0089] As examples of types or groups of polyepoxides that can be polymerized in the present invention, mention may be made of: glycidyl ethers of polyols and polyphenols; glycidyl esters of polycarboxylic acids; and epoxidized polyethylenically unsaturated hydrocarbons, esters, ethers and amides.

[0090] Suitable diglycidyl ether compounds may be aromatic, aliphatic, or alicyclic in nature and may thus be derived from dihydric phenols and diols. In addition, useful classes of such diglycidyl ethers are: diglycidyl ethers of aliphatic and alicyclic diols such as 1,2-ethanediol, 1,4-butanediol, 1,6-hexanediol, 1,8-octanediol, 1,12-dodecanediol, cyclopentanediol and cyclohexanediol; diglycidyl ethers based on bisphenol A; bisphenol F diglycidyl ether; diglycidyl phthalate, diglycidyl isophthalate, and diglycidyl terephthalate; diglycidyl ethers based on polyalkylene glycols, in particular polypropylene glycol diglycidyl ether; and glycidyl ethers based on polycarbonate diols. Other suitable diepoxides that may also be mentioned include: diunsaturated fatty acids C1-C 18 Alkyl ester diepoxides; butadiene diepoxides; polybutadiene diglycidyl ether; vinyl cyclohexene diepoxides; and limonene diepoxides.

[0091] Additional illustrative polyepoxides include, but are not limited to: glycerol polyglycidyl ether; trimethylolpropane polyglycidyl ether; pentaerythritol polyglycidyl ether; diglycerol polyglycidyl ether; polyglycerol polyglycidyl ether; and sorbitol polyglycidyl ether.

[0092] In addition, highly preferred examples of polyepoxides include: bisphenol A epoxy resins, such as DER TM 331、DER TM 330、DER TM 337 and DER TM 383; Bisphenol F epoxy resin, such as DER TM 354; Bisphenol A / F epoxy resin blends, such as DER TM 353; Aliphatic glycidyl ethers, such as DER TM 736; Polypropylene glycol diglycidyl ether, such as DER TM 732; Solid bisphenol A epoxy resin, such as DER TM 661 and DER TM 664UE; Solutions of solid bisphenol A epoxy resins, such as DER TM 671-X75; Epoxy novolac resin, such as DEN TM 438; Brominated epoxy resins, such as DER TM542; Castor oil triglycidyl ether, such as ERISYS TM GE-35H; Polyglycerol-3-polyglycidyl ether, such as ERISYS TM GE-38; and sorbitan glycidyl ether, such as ERISYS TM GE-60.

[0093] In addition to the above, in certain embodiments, the composition may include a glycidyloxyalkylalkoxysilane having the formula:

[0094]

[0095] wherein: each R is independently selected from methyl or ethyl; and

[0096] n is 1 to 10.

[0097] Exemplary silanes include, but are not limited to, γ-glycidoxypropyltrimethoxysilane, γ-glycidoxyethyltrimethoxysilane, γ-glycidoxymethyltrimethoxysilane, γ-glycidoxymethyltriethoxysilane, γ-glycidoxyethyltriethoxysilane, γ-glycidoxypropyltriethoxysilane, and 8-glycidoxyoctyltrimethoxysilane. When present, the epoxy-functional silane should comprise less than 20 wt%, preferably less than 10 wt%, or less than 5 wt%, based on the total weight of the epoxy compound.

[0098] The present invention also does not exclude that the curable composition further comprises one or more cyclic monomers selected from the group consisting of oxetanes; cyclic carbonates; cyclic anhydrides; and lactones. The disclosures of the following citations may be instructive in disclosing suitable cyclic carbonate functional compounds: U.S. Patent No. 3,535,342; U.S. Patent No. 4,835,289; U.S. Patent No. 4,892,954; British Patent No. GB-A-1,485,925; and EP-A-0 119 840. However, such cyclic comonomers should account for less than 20% by weight, preferably less than 10% by weight or less than 5% by weight, based on the total weight of the epoxy compound.

[0099] Curing agent

[0100] The invention provides for the presence in the composition of a curing agent consisting of one or more compounds having at least one epoxy-reactive group and having no disulfide functional groups.

[0101] It is not intended to particularly limit the curing agent that can be used in the present invention. For example, the curing agent can include one or more compounds or be composed of one or more compounds, and the compound per molecule has at least two epoxy reactive groups. Similarly, the curing agent can include a latent curing agent or be composed of a latent curing agent, and the latent curing agent includes a photolatent curing agent. In the context of the present invention, it is envisioned that the combination of reactive curing agents and latent curing agents. In addition, the amount of the curing agent present in the composition should be sufficient to achieve complete curing of one or more epoxy compounds.

[0102] More specifically, the amount of curing agent present in the composition should be such that the composition is characterized by a molar ratio of epoxy-reactive groups to epoxy groups of 0.6:1 to 1.2:1, e.g., 0.6:1 to 1.1:1, 0.7:1 to 1:1, or 0.75:1 to 1:1. Notably, a molar ratio of epoxy-reactive groups to epoxy groups of 1:1 is included within these stated ranges. A highly preferred molar ratio of epoxy-reactive groups to epoxy groups provides an excess of epoxy-reactive groups and is from 0.75:1 to 0.95:1. For assurance, the term epoxy-reactive groups includes latent reactive groups, which are thus included in this molar ratio term; and, as will be described below, the healing agent can contribute to the total amount of epoxy-reactive groups present in the composition.

[0103] In a supplementary statement of the composition ingredients, preferably, based on the weight of the composition, the composition comprises 0.01 to 25 wt % of the curing agent for one or more of the epoxy compounds. Preferably, the composition comprises 5 to 25 wt %, for example 5 to 20 wt % of the curing agent.

[0104] The reactive curing agent may include, inter alia, one or more of: i) at least one polyamine having at least two amine hydrogens reactive toward epoxy groups; ii) at least one mercapto compound having at least two mercapto groups reactive toward epoxy groups; and iii) at least one Mannich base.

[0105] The at least one polyamine having at least two amine hydrogens reactive toward epoxy groups should in particular contain primary and / or secondary amine groups and the equivalent weight per primary or secondary amine group should not exceed 150 g / equivalent, more preferably not exceed 125 g / equivalent.

[0106] Suitable polyamines that may be used alone or in combination include, but are not limited to, the following:

[0107] i) aliphatic, cycloaliphatic or arylaliphatic primary diamines, examples of which may be mentioned: 2,2-dimethyl-1,3-propylenediamine; 1,3-pentanediamine (DAMP); 1,5-pentanediamine; 1,5-diamino-2-methylpentane (MPMD); 2-butyl-2-ethyl-1,5-pentanediamine (C11-neodiamine); 1,6-hexanediamine (hexamethylenediamine, HMDA); 2,5-dimethyl-1,6-hexanediamine; 2,2,4-trimethylhexamethylenediamine and / or 2,4,4-trimethylhexamethylenediamine; 1,7-heptanediamine; 1,8-octanediamine; 1,9-nonanediamine; 1,10-decanediamine; 1,11-undecanediamine; 1,12-dodecanediamine; 1,2-diaminocyclohexane, 1,3-Diaminocyclohexane and 1,4-diaminocyclohexane; bis(4-aminocyclohexyl)methane; bis(4-amino-3-methylcyclohexyl)methane; bis(4-amino-3-ethylcyclohexyl)methane; bis(4-amino-3,5-dimethylcyclohexyl)methane; bis(4-amino-3-ethyl-5-methylcyclohexyl)methane; 1-amino-3-aminomethyl-3,5,5-trimethylcyclohexane (isophoronediamine, IPDA); 2-methyl-1,3-diaminocyclohexane and / or 4-methyl-1,3-diaminocyclohexane; 1,3-bis(aminomethyl)-cyclohexane; 1,4-bis(aminomethyl)cyclohexane; 2,5(2,6)-bis(aminomethyl)-bicyclo[2.2.1]heptane (norborane diamine diamine), NBDA); 3(4),8(9)-bis(aminomethyl)tricyclo[5.2.1.0 2,6 ]-decane (TCD-diamine); 1,4-diamino-2,2,6-trimethylcyclohexane (TMCDA); 1,8-menthane diamine; 3,9-bis(3-aminopropyl)-2,4,8,10-tetraoxaspiro[5.5]undecane; and 1,3-bis(aminomethyl)benzene (MXDA).

[0108] ii) tertiary amine group-containing polyamines having two or three aliphatic primary amine groups, of which the following specific examples may be mentioned: N,N'-bis(aminopropyl)-piperazine; N,N-bis(3-aminopropyl)methylamine; N,N-bis(3-aminopropyl)ethylamine; N,N-bis(3-aminopropyl)propylamine; N,N-bis(3-aminopropyl)cyclohexylamine; N,N-bis(3-aminopropyl)-2-ethyl-hexylamine; tris(2-aminoethyl)amine; tris(2-aminopropyl)amine; tris(3-aminopropyl)amine; and products from double cyanoethylation and subsequent reduction of fatty amines derived from natural fatty acids, such as N,N-bis(3-aminopropyl)dodecylamine and N,N-bis(3-aminopropyl)tallowalkylamine, which can be used as Y12D and YT (from Akzo Nobel) was commercially available.

[0109] iii) aliphatic primary polyamines containing ether groups, of which the following specific examples may be mentioned: bis(2-aminoethyl) ether; 3,6-dioxaoctane-1,8-diamine; 4,7-dioxadecane-1,10-diamine; 4,7-dioxadecane-2,9-diamine; 4,9-dioxadodecane-1,12-diamine; 5,8-dioxadodecane-3,10-diamine; 4,7,10-trioxatridecane-1,13-diamine and higher oligomers of these diamines; bis(3-aminopropyl)polytetrahydrofuran and other polytetrahydrofuran diamines; alicyclic ether group-containing diamines obtained by propoxylation and subsequent amination of 1,4-dimethylolcyclohexane, such as those which can be used as RFD-270 (from Huntsman) is a material commercially available; polyoxyalkylene diamines or polyoxyalkylene triamines, which are available as products from the amination of polyoxyalkylene diols and polyoxyalkylene triols and can be used as The name of the polyetheramine (from BASF) or PC It is commercially available under the name of (from Nitroil). It can be noted that it is particularly preferred to use D-230, D-400, D-600, D-2000, D-4000, T-403, T-3000, T-5000, EDR-104, EDR-148 and EDR-176, and the corresponding amines from BASF or Nitroil.

[0110] iv) primary diamines having secondary amine groups, examples of which may be mentioned: 3-(2-aminoethyl)aminopropylamine, bis(hexamethylene)triamine (BHMT); diethylenetriamine (DETA); triethylenetetramine (TETA); tetraethylenepentamine (TEPA); pentaethylenehexamine (PEHA); higher homologues of linear polyethyleneamines, such as polyethylenepolyamines having 5 to 7 ethyleneamine units (so-called “higher ethylenepolyamines”, HEPA); products from multiple cyanoethylation or cyanobutylation of primary diamines and polyamines having at least two primary amine groups and subsequent hydrogenation, said Primary diamines and polyamines such as dipropylenetriamine (DPTA), N-(2-aminoethyl)-1,3-propylenediamine (N3-amine), N,N'-bis(3-aminopropyl)ethylenediamine (N4-amine), N,N'-bis(3-aminopropyl)-1,4-diaminobutane, N5-(3-aminopropyl)-2-methyl-1,5-pentanediamine, N3-(3-aminopentyl)-1,3-pentanediamine, N5-(3-amino-1-ethylpropyl)-2-methyl-1,5-pentanediamine, or N,N'-bis(3-amino-1-ethylpropyl)-2-methyl-1,5-pentanediamine.

[0111] v) Polyamines having one primary and at least one secondary amino group, examples of which may be mentioned are: N-butyl-1,2-ethylenediamine; N-hexyl-1,2-ethylenediamine; N-(2-ethylhexyl)-1,2-ethylenediamine; N-cyclohexyl-1,2-ethylenediamine; 4-aminomethylpiperidine; N-(2-aminoethyl)piperazine; N-methyl-1,3-propylenediamine; N-butyl-1,3-propylenediamine; N-(2-ethylhexyl)-1,3-propylenediamine; N-cyclohexyl-1,3-propylenediamine; 3-methylamino-1-pentylamine; 3-ethylamino-1-pentylamine; 3-cyclohexylamino-1-pentylamine; fatty diamines, such as N-cocoalkyl-1,3-propylenediamine; polyamines derived from aliphatic primary diamines with acrylonitrile, maleic acid diesters or fumaric acid diesters, citraconic acid diesters , products of Michael-type addition reactions of acrylates and methacrylates, acrylic and methacrylic acid amides and itaconic acid diesters in a 1:1 molar ratio; products from the partial reductive alkylation of primary polyamines with aldehydes or ketones, especially the N-monoalkylation products of the previously mentioned polyamines having two primary amino groups, in particular 1,6-hexanediamine, 1,5-diamino-2-methylpentane, 1,3-bis(aminomethyl)cyclohexane, 1,4-bis(aminomethyl)cyclohexane, 1,3-bis(aminomethyl)benzene, BHMT, DETA, TETA, TEPA, DPTA, N3-amine and N4-amine, wherein preferred alkyl groups are benzyl, isobutyl, hexyl and 2-ethylhexyl; and partially styrylated polyamines, such as can be 240 (from Mitsubishi Gas Chemical) are commercially available.

[0112] vi) N,N′-dialkylation products of secondary diamines, in particular the previously mentioned polyamines having two primary amino groups, especially 1,6-hexanediamine, 1,5-diamino-2-methylpentane, 1,3-bis(aminomethyl)cyclohexane, 1,4-bis(aminomethyl)-cyclohexane, 1,3-bis(aminomethyl)benzene, BHMT, DETA, TETA, TEPA, DPTA, N3-amine or N4-amine, wherein preferred alkyl groups are 2-phenylethyl, benzyl, isobutyl, hexyl and 2-ethylhexyl.

[0113] vii) Aromatic polyamines, the following may be mentioned: m-phenylenediamine and p-phenylenediamine; 4,4'-diaminodiphenylmethane, 2,4'-diaminodiphenylmethane and 2,2'-diaminodiphenylmethane; 3,3'-dichloro-4,4'-diaminodiphenylmethane (MOCA); 2,4-toluenediamine and 2,6-toluenediamine; a mixture of 3,5-dimethylthio-2,4-toluenediamine and 3,5-dimethylthio-2,6-toluenediamine (which may be 300 from Albermarle); a mixture of 3,5-diethyl-2,4-toluenediamine and 3,5-diethyl-2,6-toluenediamine (DETDA); 3,3',5,5'-tetraethyl-4,4'-diaminodiphenylmethane (M-DEA); 3,3',5,5'-tetraethyl-2,2'-dichloro-4,4'-diaminodiphenylmethane (M-CDEA); 3,3'-diisopropyl-5,5'-dimethyl-4,4'-diaminodiphenylmethane (M-MIPA ); 3,3',5,5'-tetraisopropyl-4,4'-diaminodiphenylmethane (M-DIPA); 4,4'-diaminodiphenyl sulfone (DDS); 4-amino-N-(4-aminophenyl)benzenesulfonamide; 5,5'-methylenedi-o-aminobenzoic acid; dimethyl-(5,5'-methylenedi-o-aminobenzoate); 1,3-propylene-bis(4-aminobenzoate); 1,4-butylene-bis(4-aminobenzoate); polytetramethylene oxide-bis(4-aminobenzoate) (which can be Available from Air Products); 1,2-bis(2-aminophenylthio)ethane, 2-methylpropyl-(4-chloro-3,5-diaminobenzoate); and tert-butyl-(4-chloro-3,5-diaminobenzoate).

[0114] viii) Polyamidoamines, indicative members of which include the reaction products of monocarboxylic acids or polycarboxylic acids or their esters or anhydrides (especially dimer fatty acids) with aliphatic, cycloaliphatic or aromatic polyamines (e.g. polyalkyleneamines such as DETA or TETA). Commercially available polyamidoamines include: 100, 125, 140 and 150 (from Cognis); 223, 250 and 848 (from Huntsman); 3607 and 530 (from Huntsman); and EH651, EH 654, EH 655, EH 661 and EH 663 (from Cytec).

[0115] Among the above-mentioned polyamines having at least two aliphatic primary amine groups, exemplary compounds are: isophoronediamine (IPDA); hexamethylenediamine (HMDA); 1,3-bis(aminomethyl)cyclohexane; 1,4-bis(aminomethyl)cyclohexane; bis(4-amino-cyclohexyl)methane; bis(4-amino-3-methylcyclohexyl)methane; NBDA; and ether-containing polyamines having a number average molecular weight (Mn) of up to 500 g / mol, commercial examples of which include D-230 and D-600 (available from Huntsman).

[0116] As mentioned above, the composition of the present invention may optionally contain at least one compound having at least two reactive thiol groups per molecule as a curing agent, provided that the curing agent does not have a disulfide functional group. Suitable thiol-containing compounds that can be used alone or in combination include, but are not limited to, the following:

[0117] - Mercaptan-terminated polyoxyalkylene ethers, which are obtainable by reaction of polyoxyalkylene diols and polyoxyalkylene triols with epichlorohydrin or with alkylene oxides and subsequent reaction with sodium hydrosulfide.

[0118] Thiol-terminated compounds in the form of polyoxyalkylene derivatives, which are marketed under the trade name (from Cognis), in particular its models WR-8, LOF and 3-800.

[0119] Polyesters of thiocarboxylic acids, specific examples of which include: pentaerythritol tetrathioglycolate (PETMP); trimethylolpropane trimerioglycolate (TMPMP); ethylene glycol dimerioglycolate; and esterification products of polyoxyalkylene diols and triols, ethoxylated trimethylolpropane and polyester diols with thiocarboxylic acids such as thioglycolic acid and 2-mercaptopropionic acid or 3-mercaptopropionic acid.

[0120] 2,4,6-Trimercapto-1,3,5-triazine, 2,2'-(ethylenedioxy)-diethanethiol (triethylene glycol dithiol) and / or ethanedithiol.

[0121] · Tris(2-(mercaptopropionyl)ethyl)isocyanate.

[0122] It is recognized that preference is given to using polyesters of thiocarboxylic acids, in particular using at least one of the following: pentaerythritol tetrakisthioacetate (PETMP), tris(3-mercaptopropionate) (TMP), trimethylolpropane trimercaptoacetate (TMPMP), tris(2-(mercaptopropionyl)ethyl)isocyanate and ethylene glycol dimercaptoacetate.

[0123] As mentioned above, the reactive curing agent may include at least one Mannich base. Such compounds may be characterized by containing at least one phenalkamine, particularly a phenalkamine obtained by condensation of cardanol (CAS No. 37330-39-5), an aldehyde and an amine. The reactant amine in the condensation reaction is desirably ethylenediamine or diethyltriamine.

[0124] Mannich bases and phenalkamines are known in the art, and suitable examples include: commercially available phenalkamines NC-541, NC-557, NC-558, NC-566, Lite 2001, and Lite 2002 (available from Cardolite); 3440, 3441, 3442 and 3460 (available from Huntsman); and EH 614, EH 621, EH 624, EH 628 and EH 629 (available from Cytec).

[0125] Any common latent epoxy curing agent used in the art can be used in the present invention without particular limitation. For example, suitable latent epoxy curing agents that can be used herein are described in the following: U.S. Patent No. 4,546,155; U.S. Patent No. 7,226,976; U.S. Patent No. 4,833,226; JP2008214567; British Patent No. GB ​​1,121,196; WO2014 / 165423; and U.S. Patent No. 5,077,376. In addition, examples of commercially available latent epoxy curing agents include: Amicure PN-23, PN-40, PN-H, MY-24 and PN-50 commercially available from Ajinomoto Co., Inc.; EH-4337S, EH-3293S and EH-4357S commercially available from Asahi Denka Co. Ltd.; Novacure HX-3722 and HXA-3921HP commercially available from Asahi Kasei Kogyo. KK; and Sunmide LH-210, Ancamin 2014AS / FG and Ancamin 2337S commercially available from Air Products and Chemicals, Inc.

[0126] As is known in the art, dicyandiamide is commonly used as a latent epoxy curing agent, and indeed can be used in the compositions of the present invention. When used, it is preferred that the dicyandiamide is in finely divided form: it can be noted that an average particle size (d50) of 0.5 to 100 μm, such as 1 to 50 μm or 2 to 20 μm is desired. The particle size refers to the diameter or maximum dimension of a particle in a particle distribution and can be measured by dynamic light scattering.

[0127] Other exemplary latent epoxy curing agents include, but are not limited to, ketimines obtainable by the reaction of aliphatic polyamines and ketones; polyethyleneimines, particularly polyethyleneimines having a weight average molecular weight (Mw) of 700 to 1,000,000 g / mol; imidazole derivatives, such as 2-heptadeoylimidazole, 2-phenyl-4,5-dihydroxymethylimidazole, 2-phenyl-4-methyl-5-hydroxymethylimidazole, 2-phenyl-4-benzyl-5-hydroxymethyl-imidazole; 2,4-diamino-8-2-methylimidazolyl-(1)-ethyl-5-triazine; addition products of triazine with isocyanuric acid; hydrazides, such as succinohydrazide, adipohydrazide, isophtholohydrazide, o-oxybenzohydrazide, and salicylohydrazide.

[0128] Restorative Agent

[0129] The composition of the present invention is characterized in that it comprises a repairing agent. The repairing agent consists of at least one compound containing at least one disulfide functional group and optionally at least one epoxy reactive group selected from hydroxyl, thiol, amine, or carboxyl groups.

[0130] In the absence of the optionally present epoxy-reactive groups, the healing agent will be unreactive until the reaction conditions are such that a disulfide exchange reaction occurs: this embodiment presents the possibility that the healing agent may not participate in the cure by which the initial bonding with the one-component (1K) composition is achieved, but may become activated within the cured matrix to allow the matrix to bond again to the substrate of a given assembly.

[0131] In the preferred alternative where the healing agent comprises epoxy reactive groups, the healing agent will participate in the curing by which the initial bonding is achieved. Broadly speaking, the curing reaction will produce a vitrimer, the polymeric network topology of which is obtained after the initial curing can be altered by thermally activated disulfide rearrangement.

[0132] Without being bound by theory, the initial cure involves two competing reactions: i) opening of the epoxy ring by epoxy reactive groups of the curing agent and, where applicable, epoxy reactive groups of the healing agent to form an oligomer; and ii) crosslinking reaction of the oligomer by pendant reactive groups resulting from the opening of the epoxy groups. When the healing agent contains epoxy reactive groups, these can participate in the cure reaction, and the healing agent can also increase the cure rate in certain circumstances: if the curing conditions are such that reversible cleavage and reformation of disulfide bonds occurs (usually at elevated temperatures), this increases the collision probability of epoxy groups with epoxy reactive groups in the reaction mixture. However, it is believed that the fast reaction rate may affect the network topology (e.g., the stability of the crystalline domains) in the cured resin, because the rapid increase in the viscosity of the reaction mixture reduces the mobility of the oligomers formed: these oligomers have less time to sort before the crosslinking reaction occurs.

[0133] This consideration may be a determining factor in the molar amount of disulfide bonds introduced via the healing agent containing epoxy-reactive groups: the amount of healing agent should be effective to promote matrix rearrangement upon thermal activation of the disulfide groups, but should not be so excessive as to be detrimental to the stability of the cured composition.

[0134] When formulating the curable composition, preferably, the composition comprises 0.01 to 10 wt% of the repair agent based on the weight of the composition. Preferably, the composition comprises 1 to 10 wt%, such as 2 to 8 wt% of the repair agent.

[0135] In important embodiments, the repair agent comprises or consists of a compound having the general formula (DS1):

[0136]

[0137] Where: R p and R q Independently selected from: H, halogen, C1-C 12 Alkyl, C6-C 18 Aryl, C1-C 12 Alkoxy, -(CO)R r 、-O(CO)R r 、-(SO)R r 、-NH-CO-R r 、-COOR r 、-NR r R s and halogens;

[0138] R r and R s Independently selected from: -H, C1-C 12 Alkyl and C6-C 18 aryl; and

[0139] t is an integer from 0 to 4.

[0140] Regarding the general formula (DS1), it is preferred that: R p and R q are independently selected from H, halogen, C1-C 12 Alkyl and C6-C 18 aryl; and t is an integer from 0 to 2. In a specific example: R p and R q is independently selected from H, halogen and C1-C4 alkyl; and t is an integer from 0 to 2. In addition, exemplary compounds according to formula (DS1) include, but are not limited to: bis(4-aminophenyl) disulfide; bis(2-aminophenyl) disulfide; and 2-amino-4-chlorophenyl disulfide.

[0141] In alternative embodiments, the repair agent comprises or consists of a compound having the general formula (DS2):

[0142]

[0143] Where: R g is H or C1-C6 alkyl;

[0144] R h and R i Independently selected from H, C1-C6 alkyl, COOR g , SH and OH;

[0145] R j Selected from NHR g 、COOR g , SH and OH; and

[0146] k is an integer from 0 to 10.

[0147] Regarding the general formula DS2, it is preferred that: R g H; R h is H or C1-C6 alkyl; R i Independently selected from H, C1-C6 alkyl, COOR g ,SH and OH; R j Selected from NHR g 、COOR g , SH and OH; and k is an integer from 0 to 10. In a specific example: R g H; R h H; R i Independently selected from H, C1-C6 alkyl and COOR g ; R j Selected from NHR g and COOR g ; and k is an integer from 0 to 10. In addition, exemplary compounds according to formula (DS2) include, but are not limited to: 3,3'-dithiopropionic acid; 4,4'-dithiobutyric acid; bis(10-carboxydecyl) disulfide; 2,2'-dithiobisethylamine (cystamine); and (2R)-2-amino-3-[[(2R)-2-amino-2-carboxyethyl]disulfanyl]propionic acid (L-cystine).

[0148] Other compounds having utility as healing agents include liquid thiol-terminated polysulfide polymers, commercial examples of which include: polymers (available from Morton Thiokol), particularly types LP-3, LP-33, LP-980, LP-23, LP-55, LP-56, LP-12, LP-31, LP-32, and LP-2; and G polymers (from AkzoNobel), in particular types G10, G112, G131, G1, G12, G21, G22, G44 and G4.

[0149] Accelerator

[0150] The composition of the invention should preferably contain at least one accelerator. An accelerator is a substance that accelerates the reaction between epoxy groups and epoxy-reactive groups of the curing agent and, where applicable, epoxy-reactive groups of the healing agent, for example, the reaction between amine groups or thiol groups and epoxy groups. A specific example relates to the use of amine accelerators, which act by deprotonating the reactive thiol (-SH) groups present to thiolates (-S"), which react with epoxy groups by nucleophilic ring-opening polymerization.

[0151] Without intending to limit the accelerators used in the present invention, the following suitable accelerators may be mentioned: i) acids or compounds which can be hydrolyzed into acids, in particular a) organic carboxylic acids, such as acetic acid, benzoic acid, salicylic acid, 2-nitrobenzoic acid and lactic acid; b) organic sulfonic acids, such as methanesulfonic acid, p-toluenesulfonic acid and 4-dodecylbenzenesulfonic acid; c) sulfonic acid esters; d) inorganic acids, such as phosphoric acid; e) Lewis acid compounds, such as BF3 amine complexes, SbF6 sulfonium compounds, bisarene iron complexes; f) Bronsted acid compounds, such as pentafluoroantimonic acid complexes; e) mixtures of the above acids and acid esters; ii) phenols, in particular bisphenols; ii) tertiary amines, such as 2-piperazin-1-ylethylamine, 1,4-diazabicyclo[2.2.2]octane, benzyldimethylamine, α-methylbenzyldimethylamine, triethanolamine, dimethylaminopropylamine, imidazoles (including N-methylimidazole, N-vinylimidazole and 1,2-dimethylimidazole), and salts of such tertiary amines; iii) quaternary ammonium salts, such as benzyltrimethylammonium chloride; iv) amidines, such as 1,8-diazabicyclo[5.4.0]undec-7-ene; v) guanidines, such as 1,1,3,3-tetramethylguanidine; iv) phenol resins; and v) phosphites, such as diphenyl phosphite and triphenyl phosphite.

[0152] In an embodiment, the accelerator for curing the composition based on one or more epoxy compounds can be a photobase generator: when exposed to UV radiation (usually with a wavelength of 320 to 420 nm), the photobase generator releases an amine, which catalyzes the addition of epoxy reactive groups to the epoxy compound. There is no particular limitation on the photobase generator, as long as it directly or indirectly generates an amine under light irradiation. The preparation of suitable photobase generator compounds is known in the art, and guiding references include US5,650,261 (Winkel). In addition, suitable photobase generators that can be mentioned include: benzyl carbamate; benzoin carbamate; o-carbamoylhydroxylamine; O-carbamoyl oxime; aromatic sulfonamide; α-lactam; N-(2-allyl vinyl) amide; aryl azide, N-aryl formamide and 4-(o-nitrophenyl) dihydropyridine.

[0153] In an alternative embodiment, the acid promoter may be selected from a photoacid generator (PAG): upon irradiation with light energy, an ionic photoacid generator undergoes a cleavage reaction and releases one or more molecules of a Lewis acid or a Bronsted acid, which catalyzes the ring opening and addition of pendant epoxy groups to form crosslinks. Useful photoacid generators are thermally stable, do not undergo heat-induced reactions with the formed copolymer, and are readily dissolved or dispersed in the curable composition.

[0154] Exemplary cations that can be used as the cationic portion of the ionic PAGs of the present invention include organic onium cations such as those described in U.S. Pat. No. 4,250,311, U.S. Pat. No. 3,113,708, U.S. Pat. No. 4,069,055, U.S. Pat. No. 4,216,288, U.S. Pat. No. 5,084,586, U.S. Pat. No. 5,124,417, and U.S. Pat. No. 5,554,664. These references specifically encompass onium salts centered on aliphatic or aromatic Group IVA and VIIA (CAS version) elements, noting that onium salts centered on I-, S-, P-, Se-N-, and C- are preferred, such as those selected from sulfonium oxide, iodonium, sulfonium, selenium, pyridinium, carbonium, and phosphonium.

[0155] As is known in the art, the nature of the counter anion in the ionic photoacid generator (PAG) affects the rate and extent of cationic addition polymerization of epoxy groups, and for illustration, the order of reactivity between common nucleophilic anions is SbF6>AsF6>PF6>BF4. The effect of the anion on reactivity has been attributed to three major factors that one skilled in the art should compensate for in the present invention: (1) the acidity of the protic or Lewis acid generated; (2) the extent of ion pair separation in the growing cationic chain; and (3) the susceptibility of the anion to fluoride abstraction and subsequent chain termination.

[0156] In general, the photoinitiator should be present in the photocurable composition in an amount of 0 to 5 wt %, such as 0 to 2.0 wt % or 0 to 1.5 wt %, based on the total weight of the composition.

[0157] As will be appreciated by those skilled in the art, a photosensitizer may be incorporated into the composition to increase the efficiency with which the photoinitiator uses the delivered energy. The term "photosensitizer" is used according to its standard meaning to refer to any substance that increases the rate of photoinitiated polymerization or shifts the wavelength at which polymerization occurs. When present, the photosensitizer should be used in an amount of 5 to 25 weight percent, based on the weight of the photoinitiator.

[0158] The use of one or more photoinitiators and, where applicable, one or more photosensitizers may produce residual compounds in the final cured product by photochemical reactions. The residues can be detected by conventional analytical techniques (such as: infrared spectroscopy, ultraviolet spectroscopy and NMR spectroscopy; gas chromatography or liquid chromatography; and mass spectrometry). Therefore, the present invention may include a cured matrix (co)polymer and a detectable amount of residues from at least the photoinitiator. Such residues are present in small amounts and generally do not interfere with the desired physicochemical properties of the final cured product.

[0159] Without intending to limit the invention, a mixture containing one or more photoinitiators may be irradiated with activating radiation to polymerize one or more monomer components contained therein. The purpose of irradiation is to generate an active species from the photoinitiator that initiates the curing reaction. Once this species is generated, the curing chemistry follows the same thermodynamic rules as any chemical reaction: the reaction rate can be accelerated by heat.

[0160] Those skilled in the art will recognize that the choice of accelerator is not simply related to the accelerator that adds the fastest. Other factors that are decisive in the choice of accelerator include: cost; toxicity; solubility; processing effects, such as working time, premature gelation, exothermic degradation, expansion and outgassing; final properties, such as glass transition temperature (T g ), modulus, strength, elongation at break, and chemical resistance; regulatory issues; and ease of use.

[0161] In the present invention, it is preferred to use an accelerator comprising or consisting of at least one tertiary amine, at least one amidine, or a mixture thereof. More particularly, the accelerator should be selected from imidazole, methylimidazole, benzyldimethylamine, 1,8-diazabicyclo[5.4.0]undec-7-ene, 1,4-diazabicyclo(2,2,2)octane, and mixtures thereof.

[0162] The accelerator should desirably be present in the composition in an amount of 0.1 to 5 wt % based on the weight of the composition: the accelerator may preferably comprise 1 to 2 wt %, for example 0.1 to 1 wt % of the composition.

[0163] Electrolytes

[0164] The composition comprises 0.5 to 15 wt % electrolyte based on the weight of the composition: the electrolyte may preferably account for 0.5 to 10 wt %, for example 0.5 to 5 wt % of the composition. These amounts are preferred because an amount of electrolyte greater than 15 wt % based on the weight of the composition may produce a good debonding effect, but curing will be incomplete and thus the initial adhesive properties will be adversely affected. On the contrary, at an amount less than 0.5 wt % based on the weight of the composition, the debonding effect will be impaired.

[0165] The electrolyte comprises or consists of at least one salt according to formula (I) or formula (II):

[0166]

[0167] Where: R 1 , R 2 , R 3 , R 4 and R 5 independently selected from hydrogen, C1-C 18 Alkyl, C3-C 18 Cycloalkyl, C6-C 18 Aryl, C7-C 24 Aralkyl, C2-C 20 Alkenyl, -C(O)R q , -C(O)OH, -CN, or -NO2; R q is C1-C6 alkyl; and X - It is a counter anion.

[0168] For the sake of completeness, in formula (I) and formula (II), the term C1-C n Alkyl, C3-C n Cycloalkyl, C6-C 18 Aryl, C7-C 24 Aralkyl, C2-C 20 Alkenyl groups specifically include groups in which one or more hydrogen atoms are replaced by halogen atoms (e.g., C1-C 18 haloalkyl) or a group substituted with a hydroxyl group (e.g., C1-C 18 In particular, preferably, R 1 , R 2 , R 3 , R 4 and R 5 independently selected from hydrogen, C1-C 18 Alkyl, C1-C 18 Halogenated alkyl, C1-C 18 Hydroxyalkyl, or C3-C 18 Cycloalkyl. For example, R 1 , R 2 , R 3 , R 4 and R 5 can be independently selected from hydrogen, C1-C 18 Alkyl, or C1-C 18 Halogenated alkyl.

[0169] There is no intention to particularly limit the counter anions (X) that can be used in the electrolyte. –). Exemplary anions may be selected from:

[0170] ·Halide;

[0171] Formula PF6 - CF3SO3 - 、(CF3SO3)2N - CF3CO2 - and CCl3CO2 - Pseudohalide ions and halogen-containing compounds;

[0172] ·CN - 、SCN - and OCN - ;

[0173] Phenol root (phenate);

[0174] ·General formula SO4 2- 、HSO4 - 、SO3 2- 、HSO3 - , R a OSO3 - and R a SO3 - of sulfate, sulfite and sulfonate;

[0175] General formula PO4 3- 、HPO4 2- 、H2PO4 - , R a PO4 2- , HR a PO4 - and R a R b PO4 - of phosphate;

[0176] General formula R a HPO3 - , R a R b PO2 - and R a R b PO3 - phosphonate and phosphinate;

[0177] General formula PO3 3- 、HPO3 2- 、H2PO3 - , R a PO3 2- , Ra HPO3 – and R a R b PO3 - of phosphite;

[0178] General formula R a R b PO2 - , R a HPO2 - , R a R b PO - and R a HPO - of phosphonite and phosphinite;

[0179] General formula R a COO - The carboxylate anion;

[0180] Hydroxycarboxylic acid anions and sugar acid anions;

[0181] Saccharin salt (salt of sulfonylimide phthalate);

[0182] General formula BO3 3- , HBO3 2- 、H2BO3 - , R a R b BO3 - , R a HBO3 - , R a BO3 2- , B(OR a )(OR b )(OR c )(OR d ) - 、B(HSO4) - and B(R a SO4) - borate;

[0183] General formula R a BO2 2- and R a R b BO - boronate;

[0184] General formula HCO3 - 、CO3 2- and R a CO3- carbonates and carbonate esters;

[0185] General formula SiO4 4- 、HSiO4 3- 、H2SiO4 2- 、H3SiO4 - , R a SiO4 3- , R a R b SiO4 2- , R a R b R c SiO4 - , HR a SiO4 2- 、H2R a SiO4 – and HR a R b SiO4 - Silicates and silicates;

[0186] General formula R a SiO3 3- , R a R b SiO2 2- , R a R b R c SiO - , R a R b R c SiO3 - , R a R b R c SiO2 – and R a R b SiO3 2- Alkyl- and arylsilanolates;

[0187] Pyridinate and pyrimidinate;

[0188] Carboxylic acid imides, bis(sulfonyl)imides and sulfonyl imides of the following general formula:

[0189]

[0190] Methyl compounds of the following general formula:

[0191]

[0192] General formula R a O - alkoxide and aryloxide; and

[0193] ·General formula S 2- , HS - , [S v ] 2- , [HS v ] - and [R a S] - sulfide, hydrogensulfide, polysulfide, hydrogen polysulfide and thiolate,

[0194] In this general formula,

[0195] v is a positive integer from 2 to 10; and

[0196] R a , R b , R c and R d independently selected from hydrogen, C1-C 12 Alkyl, C5-C 12 Cycloalkyl, C5-C 12 Heterocycloalkyl, C6-C 18 Aryl and C5-C 18 Heteroaryl.

[0197] In an embodiment, the counter anion (X - ) is preferably selected from: general formula R a OSO3 - Sulfate; general formula R a SO3 - Sulfonate radical; general formula R a PO4 2- , HR a PO4 - and R a R b PO4 - Phosphate; general formula R a HPO3 - , R a R b PO2 - and R a R b PO3 - Phosphonate and phosphinate; general formula PO3 3- 、HPO32- 、H2PO3 - , R a PO3 2- , R a HPO3 – and R a R b PO3 - Phosphite; general formula R a R b PO2 - , R a HPO2 - , R a R b PO - and R a HPO - Phosphites and phosphinates; and carboxylic acid imides, bis(sulfonyl)imides and sulfonyl imides of the following general formula:

[0198]

[0199] Where R a and R b As defined above.

[0200] Regarding the counter anion (X - ), preferably, R a and R b independently selected from hydrogen, C1-C 12 Alkyl, or C1-C 12 For example, R a and R b may be independently selected from hydrogen, C1-C8 alkyl, or C1-C8 haloalkyl, or R a and R b can be independently selected from hydrogen, C1-C4 alkyl, or C1-C4 haloalkyl. Particularly preferred counter anions (X - ) are methyl sulfate, ethyl sulfate, methane sulfonate, bis(trifluoromethylsulfonyl)imide and diethyl phosphate.

[0201] The electrolyte of the composition is preferably selected from: 1-ethyl-3-methyl-1H-imidazol-3-ium methane sulfonate; 1-ethyl-3-methyl-1H-imidazol-3-ium methyl sulfate; 1-methylimidazolium bis(trifluoromethylsulfonyl)imide; 3-methylimidazolium bis(trifluoromethylsulfonyl)imide; 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide; 1-propyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide; 1-butyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide; 1-butyl-2,3-dimethylimidazolium bis(trifluoromethylsulfonyl)imide; 1-hexyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide; 1-octyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide; Imidazolium bis(trifluoromethylsulfonyl)imide; 1-methyl-3-octylimidazolium bis(trifluoromethylsulfonyl)imide; 1-decyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide; 1-dodecyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide; tetraethylphosphonium bis(trifluoromethylsulfonyl)imide; tetrabutylphosphonium bis(trifluoromethylsulfonyl)imide; tetraoctylphosphonium bis(trifluoromethylsulfonyl)imide; trihexyl(tetradecyl)phosphonium bis(trifluoromethylsulfonyl)imide; tridecyl(tetradecyl)phosphonium bis(trifluoromethylsulfonyl)imide; tributyl(methyl)phosphonium diethyl phosphate; tributyl(ethyl)phosphonium diethyl phosphate; tetraoctylphosphonium diethyl phosphate; and mixtures thereof. As particularly preferred use may be made of at least one of 1-ethyl-3-methyl-1H-imidazol-3-ium methanesulfonate, 1-ethyl-3-methyl-1H-imidazol-3-ium methylsulfate, trihexyl(tetradecyl)phosphonium bis(trifluoromethylsulfonyl)imide, tributyl(methyl)phosphonium diethyl phosphate and tributyl(ethyl)phosphonium diethyl phosphate.

[0202] The presence of compatible electrolytic compounds that do not conform to formula (I) or formula (II) in the electrolyte is not excluded. However, the one or more compounds of formula (I) or formula (II) should account for at least 90% by weight of the electrolyte, preferably at least 95% by weight, more preferably at least 99% by weight, and most preferably 100% by weight.

[0203] Rheology Control Agents

[0204] The compositions of the present invention will conventionally comprise a rheology control agent consisting of: a non-conductive filler; a conductive filler; or a mixture thereof.

[0205] The presence of non-conductive fillers in the composition can be used to adjust the viscosity of the composition and reduce the thermal expansion coefficient of the adhesive. In general, it is not intended to particularly limit the shape of the particles used as non-conductive fillers: needle-shaped, spherical, ellipsoidal, cylindrical, beaded, cubic or flaky particles can be used alone or in combination. In addition, it is envisioned that agglomerates of more than one particle type can be used. Likewise, it is not intended to particularly limit the size of the particles used as non-conductive fillers. However, such non-conductive fillers will conventionally have an average volume particle size of 0.01-1500 μm, such as 0.1-1000 μm or 0.1-500 μm as measured by laser diffraction / scattering methods.

[0206] Exemplary non-conductive fillers include, but are not limited to, barium sulfate, calcium carbonate, calcium oxide, calcium metasilicate, silicon dioxide, fumed silica, sand, quartz, zeolite, bentonite, magnesium carbonate, diatomaceous earth, aluminum oxide, clay, talc, flint, mica, glass powder, zinc oxide and other ground minerals. Short fibers such as glass fibers, glass fibers, polyacrylonitrile, carbon fibers, polyethylene fibers may also be added. It may be noted that the non-conductive fillers initially preferred are selected from the following: calcium carbonate; calcium oxide; calcium metasilicate; talc; fumed silica; silicon dioxide; barium sulfate; and mixtures thereof. It is particularly preferred to use precipitated silica and / or fumed (pyrogenic) silica as rheology control agents in the compositions of the present invention: such precipitated silica or pyrogenic silica should desirably have a rheology control agent of 25-500 m 2 / g, for example 100-250m 2 / g of BET surface area as measured by means of nitrogen adsorption in accordance with DIN 66131. ​​A commercial example of such a fumed (pyrogenic) silica is Aerosil 200, available from Evonik Industries.

[0207] Also suitable as non-conductive fillers are hollow spheres with a mineral shell or a plastic shell. These are available, for example, under the trade name Glass Commercially available hollow glass spheres. Plastic-based hollow spheres (such as or ) can be used and are described in EP 0 520 426 B1: they are made of inorganic or organic substances and each have a diameter of 1 mm or less, preferably 500 μm or less, preferably 100 μm to 200 μm.

[0208] Non-conductive fillers which impart thixotropy to the composition may be useful in certain applications: such fillers are also described as rheology modifiers, for example hydrogenated castor oil, fatty acid amides, or expandable plastics such as PVC.

[0209] As indicated, the composition according to the invention may additionally comprise a conductive filler as at least part of the rheology control agent. In general, it is not intended to particularly limit the shape of the particles used as conductive fillers: needle-shaped, spherical, ellipsoidal, cylindrical, bead-shaped, cubic or plate-shaped particles may be used alone or in combination. In addition, it is envisaged that agglomerates of more than one particle type may be used. Likewise, it is not intended to particularly limit the size of the particles used as conductive fillers. However, such conductive fillers will conventionally have an average volume particle size as measured by laser diffraction / scattering methods of 1-500 μm, for example 1-200 μm.

[0210] Exemplary conductive fillers include, but are not limited to, silver; copper; gold; palladium; platinum; nickel; gold-plated nickel or silver-plated nickel; carbon black; carbon fiber; carbon nanotubes; graphite; aluminum; indium tin oxide; silver-plated copper; silver-plated aluminum; metal-plated glass spheres; metal-plated fillers; metal-plated polymers; silver-plated fibers; silver-plated spheres; antimony-doped tin oxide; conductive nanospheres; nanosilver; nanoaluminum; nanocopper; nanonickel; carbon nanotubes; and mixtures thereof. Preferably, particulate silver and / or carbon black are used as conductive fillers.

[0211] The total amount of rheology control agent present in the composition of the present invention will preferably be 1-55 wt%, more preferably 15-55 wt%, based on the total weight of the composition. The desired viscosity of the curable composition formed when its ingredients are mixed will generally determine the total amount of rheology control agent added. The viscosity of the composition should desirably be 3000 to 150000 mPa.s, for example 5000 to 100000 mPa.s: within such a viscosity range, the composition should be easily extruded from a suitable dispensing device (such as a tube).

[0212] Additives and auxiliary ingredients

[0213] The compositions obtained in the present invention will generally also contain adjuvants and additives that can impart improved properties to these compositions. For example, adjuvants and additives can impart one or more of the following: improved elasticity; improved elastic recovery; longer permissible processing time; faster curing time; and lower residual viscosity. Such adjuvants and additives include: solubilizers; tougheners; plasticizers; stabilizers, including UV stabilizers; antioxidants; reactive diluents; desiccants; adhesion promoters; bactericides; flame retardants; colored pigments or color pastes; and / or optionally, non-reactive diluents to a small extent.

[0214] Such adjuvants and additives can be used in such combinations and proportions as desired, provided that they do not adversely affect the characteristics and basic properties of the composition. Although there are exceptions in some cases, these adjuvants and additives should not account for more than 50% by weight of the total composition, and preferably should not account for more than 20% by weight of the composition.

[0215] Based on the weight of the composition, the solubilizer may account for 0 to 15 wt %, for example 1 to 10 wt % or 1 to 5 wt %. The solubilizer has the function of promoting the miscibility of the electrolyte in the adhesive composition: the solubilizer may or may not constitute a part of the polymer matrix formed when the adhesive composition is cured, but it is indeed used to promote ion transfer therein. Therefore, the solubilizer is preferably a polar compound and should desirably be liquid at room temperature.

[0216] Suitable solubilizing agents include: polyphosphazenes; polymethylene sulfides; polyoxyalkylene glycols; polyethylene imines; silicone surfactants such as polyalkylsiloxanes and polyoxyalkylene-modified polydimethylsiloxanes, including but not limited to poly(C2-C3)oxyalkylene-modified polydimethylsiloxanes; polyols; and sugars. For the sake of completeness, fluorinated silicone surfactants (such as fluorinated polysilanes) are intended to be included in the term silicone surfactants.

[0217] Polyols and sugars, such as ethylene glycol, 1,3-propylene glycol, cyclohexanediol, hydroquinone, catechol, resorcinol, phloroglucinol, pyrogallol, hydroxyhydroquinone, tris(hydroxymethyl)benzene, tris(hydroxymethyl)benzene having three methyl or ethyl substituents bonded to the remaining benzene carbon atoms, isosorbide, isomannide, isoidide, glycerol, cyclohexane-1,2,4-triol, 1,3,5-cyclohexanetriol, pentane- 1,2,3-triol, hexane-1,3,5-triol, erythritol, 1,2,4,5-tetrahydroxybenzene, threitol, arabitol, xylitol, ribitol, mannitol, sorbitol, inositol, fructose, glucose, mannose, lactose, 1,1,1-tri(hydroxymethyl)propane, 1,1,1-tri(hydroxymethyl)ethane, di(trihydroxymethylpropane), trimethylolpropane ethoxylate, 2-hydroxymethyl-1,3-propanediol, pentaerythritol allyl ether and pentaerythritol.

[0218] Among the polyoxyalkylene glycols, it may be noted that polyoxy (C2-C3) alkylene glycols having a weight average molecular weight of 200 to 10 000 g / mol, for example 200 to 2000 g / mol, are particularly preferably used.

[0219] The optional presence of a toughening agent (in an amount up to 10% by weight based on the weight of the composition) can facilitate debonding of the cured adhesive in certain embodiments. Without intending to be bound by theory, the toughening agent can promote phase separation within the cured adhesive under applied potential conditions. Exemplary toughening agents can be selected from: epoxy-elastomer adducts; and toughened rubbers in the form of core-shell particles dispersed in an epoxy resin matrix.

[0220] The elastomer-containing adduct may be used alone, or a combination of two or more specific adducts may be used. In addition, each adduct may be independently selected from a solid adduct or a liquid adduct at a temperature of 23°C. Typically, useful adducts will be characterized by a weight ratio of epoxy resin to elastomer of 1:5 to 5:1, such as 1:3 to 3:1. In addition, a guiding reference for suitable epoxy resin / elastomer adducts is U.S. Patent Publication 2004 / 0204551. In addition, exemplary commercial epoxy resin / elastomer adducts for use herein include, but are not limited to: HYPDX RK8-4, commercially available from CVC Chemical; and B-Tough A3, available from Croda Europe Limited.

[0221] The term "core-shell rubber" or CSR is used according to its standard meaning in the art to denote a rubber particle core formed by a polymer (which contains an elastomeric polymer or a rubbery polymer as a major component) and a shell formed by the polymer graft polymerized onto the core. The shell partially or completely covers the surface of the rubber particle core during the graft polymerization process. By weight, the core should account for at least 50% by weight of the core-shell rubber particle.

[0222] The polymer material of the core should have a glass transition temperature (T g ), preferably a glass transition temperature (T ) of -20°C or lower, more preferably -40°C or lower, even more preferably -60°C or lower g The polymer of the shell has a glass transition temperature (T g ) is a non-elastomeric, thermoplastic or thermosetting polymer above room temperature, preferably above 30°C, more preferably above 50°C.

[0223] Without intending to limit the invention, the core may be composed of: diene homopolymers, such as homopolymers of butadiene or isoprene; diene copolymers, such as copolymers of butadiene or isoprene with one or more ethylenically unsaturated monomers, such as vinyl aromatic monomers, (meth)acrylonitrile or (meth)acrylates; polymers based on (meth)acrylate monomers, such as polybutyl acrylate; and polysiloxane elastomers, such as polydimethylsiloxane and crosslinked polydimethylsiloxane.

[0224] Similarly, without intending to limit the invention, the shell may consist of a polymer or copolymer of one or more monomers selected from: (meth)acrylates, such as methyl methacrylate; vinyl aromatic monomers, such as styrene; vinyl cyanides, such as acrylonitrile; unsaturated acids and anhydrides, such as acrylic acid; and (meth)acrylamide. The polymer or copolymer used in the shell may have acid groups that are ionically crosslinked by metal carboxylate formation, in particular by forming salts of divalent metal cations. The shell polymer or copolymer may also be covalently crosslinked by monomers having two or more double bonds per molecule.

[0225] Preferably, any included core-shell rubber particles have an average particle size (d50) of 10 nm to 300 nm, for example 50 nm to 250 nm: the particle size refers to the diameter or maximum dimension of the particle in the particle distribution and is measured via dynamic light scattering. For the sake of completeness, the present application does not exclude the presence of two or more types of core-shell rubber (CSR) particles having different particle size distributions in the composition to provide a balance of key properties of the resulting cured product, including shear strength, peel strength and resin fracture toughness.

[0226] The core-shell rubber may be selected from commercially available products, examples of which include: Paraloid EXL 2650A, EXL 2655 and EXL2691 A available from The Dow Chemical Company; XT100; available from Kaneka Corporation MX series, in particular MX 120, MX 125, MX 130, MX 136, MX 551, MX553; and METABLEN SX-006 available from Mitsubishi Rayon.

[0227] A "plasticizer" for the purposes of the present invention is a substance that reduces the viscosity of the composition and thereby promotes its processability. In this context, the plasticizer may represent up to 10% by weight or up to 5% by weight, based on the total weight of the composition, and is preferably selected from: diurethanes; monofunctional, linear or branched C4-C 16Ethers of alcohols, such as Cetiol OE (available from Cognis Deutschland GmbH, Düsseldorf); rosin esters, butyrates, thiobutyrates, acetates, propionates and citrates; esters based on nitrocellulose and polyvinyl acetate; fatty acid esters; dicarboxylic acid esters; esters of fatty acids with OH groups or epoxidized; glycolates; benzoates; phosphates; sulfonates; trimellitates; polyether plasticizers, such as blocked polyethylene glycols or polypropylene glycols; polystyrene; hydrocarbon plasticizers; chlorinated paraffins; and mixtures thereof. It should be noted that, in principle, phthalates can be used as plasticizers, but these are not preferred due to their toxicological potential.

[0228] "Stabilizer" for the purposes of the present invention should be understood as an antioxidant, UV stabilizer, heat stabilizer, or hydrolysis stabilizer. In this context, the stabilizer may total up to 10% by weight or up to 5% by weight, based on the total weight of the composition. Standard commercial examples of stabilizers suitable for use herein include: sterically hindered phenols; thioethers; benzotriazoles; benzophenones; benzoates; cyanoacrylates; acrylates; hindered amine light stabilizer (HALS) type amines; phosphorus; sulfur; and mixtures thereof.

[0229] It should be noted that compounds having metal chelating properties may be used in the compositions of the present invention to help enhance the adhesion of the cured adhesive to the substrate surface. Also suitable for use as an adhesion promoter are the acetoacetate functionalized modified resins sold by King Industries under the trade name K-FLEX XM-B301.

[0230] In order to increase the shelf life even further, it is generally advisable to further stabilize the composition of the invention with respect to moisture permeation by using a desiccant. It is sometimes also necessary to reduce the viscosity of the adhesive or sealant composition of the invention for a particular application by using one or more reactive diluents. The total amount of reactive diluent present will generally be 0-15 wt. %, for example 0-5 wt. %, based on the total weight of the composition.

[0231] The presence of solvents and non-reactive diluents in the compositions of the invention is not excluded insofar as they can usefully adjust the viscosity of the composition. For example, but by way of illustration only, the composition may include one or more of the following: xylene; 2-methoxyethanol; dimethoxyethanol; 2-ethoxyethanol; 2-propoxyethanol; 2-isopropoxyethanol; 2-butoxyethanol; 2-phenoxyethanol; 2-benzyloxyethanol; benzyl alcohol; ethylene glycol; ethylene glycol dimethyl ether; ethylene glycol diethyl ether; ethylene glycol dibutyl ether; ethylene glycol diphenyl ether; diethylene glycol; diethylene glycol monomethyl ether; diethylene glycol monoethyl ether; diethylene glycol mono-n-butyl ether; diethylene glycol dimethyl ether; diethylene glycol diethyl ether; diethylene glycol di-n-butyl ether; propylene glycol butyl ether; propylene glycol phenyl ether; dipropylene glycol; dipropylene glycol monomethyl ether; dipropylene glycol dimethyl ether; dipropylene glycol di-n-butyl ether; N-methylpyrrolidone; diphenylmethane; diisopropylnaphthalene; petroleum fractions, such as products (available from Exxon); alkylphenols, such as tert-butylphenol, nonylphenol, dodecylphenol and 8,11,14-pentadecatrienylphenol; styrenated phenols; bisphenols; aromatic hydrocarbon resins, especially those containing phenolic groups, such as ethoxylated or propoxylated phenols; adipates; sebacates; phthalates; benzoates; organic phosphates or sulfonates; and sulfonamides.

[0232] In addition to the above, preferably, the non-reactive diluent accounts for less than 10 wt %, in particular less than 5 wt % or less than 2 wt %, based on the total weight of the composition.

[0233] Methods and Applications

[0234] To form the initial curable composition, the above ingredients are brought together and mixed. As is known in the art, to form a one-component (1K) curable composition, the ingredients of the composition are brought together and uniformly mixed under conditions that inhibit or prevent the reaction of the reactive components: as will be readily appreciated by those skilled in the art, this may include mixing conditions that limit or prevent exposure to moisture, heat or radiation, or that limit or prevent activation of latent catalysts of the ingredients. Therefore, it will generally be preferred not to mix the ingredients manually, but rather to mix in predetermined amounts by a machine (e.g., a static mixer or a dynamic mixer) under anhydrous conditions without intentional heating or light irradiation.

[0235] The initial use of a one-component (1K) curable composition in forming a first bonded structure will now be described. According to the broadest method aspect of the present invention, the above composition is applied to one or more material layers and then cured in situ. Before applying the composition, it is generally recommended to pretreat the relevant surface to remove foreign matter therefrom: if applicable, this step can promote the subsequent bonding of the composition thereto. Such treatments are known in the art and can be carried out in a single-stage or multi-stage manner consisting of, for example, one or more of the following: etching treatment with an acid suitable for the substrate and an optional oxidizing agent; ultrasonic treatment; plasma treatment, including chemical plasma treatment, corona treatment, atmospheric pressure plasma treatment and flame plasma treatment; immersion in an aqueous alkaline degreasing bath; treatment with an aqueous cleaning emulsion; treatment with a cleaning solvent (such as carbon tetrachloride or trichloroethylene); and water rinsing, preferably with deionized water or demineralized water. In those cases where an aqueous alkaline degreasing bath is used, any degreasing agent remaining on the surface should be removed by rinsing the substrate surface with deionized water or demineralized water.

[0236] In some embodiments, the adhesion of the coating composition of the present invention to a preferably pretreated substrate can be promoted by applying a primer thereto. In practice, a primer composition may be necessary to ensure effective fixation and / or curing time of the adhesive composition on an inactive substrate. Although one skilled in the art will be able to select a suitable primer, instructive references for selecting a primer include, but are not limited to, U.S. Patent No. 3,855,040; U.S. Patent No. 4,731,146; U.S. Patent No. 4,990,281; U.S. Patent No. 5,811,473; GB 2502554; and U.S. Patent No. 6,852,193.

[0237] The composition is then applied to the preferably pretreated, optionally primed surface of the substrate by conventional application methods such as: brushing; roller coating, knife application; printing methods; and spraying methods, including but not limited to air atomized spraying, air-assisted spraying, airless spraying, and high volume low pressure spraying.

[0238] As described above, the present invention provides a bonded structure comprising: a first substrate having a conductive surface; and a second substrate having a conductive surface, wherein a cured electrochemically debondable one-part (1K) adhesive composition as defined above and in the appended claims is disposed between the first substrate and the second substrate. To prepare such a structure, the adhesive composition may be applied to at least one inner surface of the first substrate and / or the second substrate, and then the two layers are subsequently contacted, optionally under applied pressure, such that the electrically debondable hot melt adhesive composition is sandwiched between the two substrates.

[0239] It is recommended that the composition be applied to the surface at a wet film thickness of 10-500 μm. Application of thinner layers within this range is more economical and provides a reduced likelihood of deleterious thick cured areas. However, strict control must be exercised when applying thinner coatings or layers to avoid the formation of discontinuous cured films.

[0240] Curing of the applied composition of the invention generally takes place at a temperature in the range of 40° C. to 200° C., preferably 50° C. to 190° C., in particular 60° C. to 180° C. Suitable temperatures depend on the specific compounds present and the desired curing rate and can be determined in each case by a person skilled in the art using simple preliminary tests, if necessary. Of course, curing at lower temperatures in the aforementioned range is advantageous because it eliminates the need to heat or cool the mixture significantly from the normally prevailing ambient temperature. However, where applicable, the temperature of the mixture formed from the respective ingredients of the one-part (1K) composition can be raised to above the mixing temperature and / or application temperature using conventional means, including microwave induction.

[0241] For the sake of completeness, it should be noted that the present invention does not exclude the initial preparation of epoxy adhesives in the form of "film adhesives." A prepolymer mixture of one or more epoxy compounds, curing agents, healing agents, electrolytes, and other desired components is applied as a coating to a plastic substrate, rolled up, and stored at a sufficiently low temperature to inhibit chemical reactions between the components. When needed, the film adhesive is removed from the low temperature environment and applied to metal or composite parts, the backing stripped off, the assembly completed, and cured in an oven or autoclave.

[0242] The initial bonding and subsequent debonding and rebonding of the composition of the present invention will be described with reference to the accompanying drawings, in which:

[0243] Figure 1a A bonded structure according to a first embodiment of the invention is shown.

[0244] Figure 1b A bonded structure according to a second embodiment of the invention is shown.

[0245] Figure 2a The initial debonding of the structure of the first embodiment is shown when an electric current is passed through the structure.

[0246] Figure 2b The initial debonding of the structure of the second embodiment is shown when an electric current is passed through the structure.

[0247] Figure 3a The reformation of a bonded structure according to a first embodiment of the invention is shown.

[0248] Figure 3bThe reformation of a bonded structure according to a second embodiment of the invention is shown.

[0249] Figure 3c The reformation of a bonded structure according to a third embodiment of the invention is shown.

[0250] As attached Figure 1a As shown in , a bonded structure is provided, wherein a cured adhesive layer (10) is disposed between two conductive substrates (11). A non-conductive material layer (12) may be disposed on the conductive substrate (11) to form a bonded structure as shown in FIG. Figure 1b . Each layer of the conductive substrate (11) is in electrical contact with a power source (13), which may be a battery or an AC-driven direct current (DC) source. The positive and negative terminals of the power source (13) are shown in a fixed position, but those skilled in the art will of course recognize that the polarity of the system can be reversed.

[0251] Two conductive substrates (11) are shown in the form of layers, which may consist in particular of: a metal film; a metal sheet; a metal mesh or grid; deposited metal particles; a resin material, which is made conductive by a conductive element disposed therein; or a conductive oxide layer. As exemplary conductive elements, silver filaments, single-walled carbon nanotubes and multi-walled carbon nanotubes may be mentioned. As exemplary conductive oxides, doped indium oxides, such as indium tin oxide (ITO); doped zinc oxide; antimony tin oxide; cadmium stannate; and zinc stannate may be mentioned. In addition to the choice of conductive material, a person skilled in the art will recognize that in the case where the conductive substrate (11) is in the form of a grid or mesh, which provides limited contact with the cured adhesive layer (10), the effectiveness of the debonding operation may be reduced.

[0252] When a voltage is applied between each conductive substrate (11), current is supplied to the adhesive composition (10) disposed therebetween. This initiates an electrochemical reaction at the interface of the substrate (11) and the adhesive composition, which should be understood to be oxidative at the positively charged interface or anodic interface and reductive at the negatively charged interface or cathodic interface. This reaction is believed to weaken the adhesive bond between the substrates, thereby allowing the debondable composition to be easily removed from the substrates.

[0253] like Figure 2a and Figure 2b As shown in , debonding occurs at the positive electrode interface, i.e., the interface between the binder composition (10) and the conductive surface (11) in electrical contact with the positive electrode. The binder bond at the interface of the two substrates can be weakened by reversing the direction of the current flow before separating the substrates.

[0254] However, it should be noted that the composition of the adhesive layer (10) can be adjusted so that debonding occurs at the positive electrode interface or the negative electrode interface or from both simultaneously. For some embodiments, the voltage applied across the two surfaces to form the anode interface and the cathode interface will cause debonding to occur simultaneously at the anode and cathode adhesive / substrate interfaces. In an alternative embodiment, if the composition is not responsive to direct current at both interfaces, the reversed polarity can be used to debond the two substrate / adhesive interfaces simultaneously. The current can be applied with any suitable waveform, provided that the debonding is allowed to proceed for a sufficient total time at each polarity. In this regard, sinusoidal waveforms, rectangular waveforms, and triangular waveforms may be suitable and may be applied by a controlled voltage source or a controlled current source.

[0255] Without intending to limit the present invention, it is believed that the debonding operation can be effectively performed when at least one and preferably two of the following conditions occur: a) an applied voltage of 0.5-100V; and b) the voltage is applied for a duration of 1 second to 60 minutes. In the case of promoting the release of the conductive substrate from the cured adhesive by applying a force (e.g., via a weight or spring), the potential may only need to be applied for about a few seconds. In some embodiments, a potential of 5V for 10 minutes is sufficient to have a debonding effect, while in some embodiments, a potential of 3.5V for 30 minutes is sufficient.

[0256] Desirably, after debonding, the adhesive composition is disposed only on the first substrate or the second substrate, meaning that one of the substrates is substantially free of adhesive.

[0257] In the present disclosure, a method of forming a second bonded structure via rebonding includes the following steps: providing a first rebonding substrate (RB1) obtained from the aforementioned electrochemical debonding step and having a residual cured adhesive composition disposed thereon; contacting the first rebonding substrate (RB1) with a second rebonding substrate (RB2) so that the residual cured adhesive composition is sandwiched therebetween; and thermally treating the residual cured adhesive composition. The term "third substrate" as claimed may be used interchangeably with the second rebonding substrate (RB2).

[0258] It is not intended to specifically limit the second re-bonded substrate (RB2) used: the composition, physicochemical properties and structure of the second re-bonded substrate (RB2) can be selected independently of the substrate used in the initial bonded structure. However, it is envisaged that the substrate (RB2) can be provided by the remaining substrate from the debonding operation so that the substrates (RB1, RB2) in the re-bonded structure correspond to the first substrate and the second substrate of the initial bonded structure. In an alternative, different substrates can be used as substrate (RB2). In this regard, the use of both conductive substrates and non-conductive substrates should be considered: the choice of the former allows repeated electrochemical debonding operations, because the anodic interface and the cathodic interface can be generated by applying a voltage across the re-bonded structure. In contrast, the selection of a non-conductive substrate as substrate (RB2) will exclude such a repeated process.

[0259] As described above, the conductive substrate (RB2) may be composed of, among others: a metal film; a metal sheet; a metal mesh or grid; deposited metal particles; a resin material which is made conductive by a conductive element disposed therein; or a conductive oxide layer. Exemplary non-conductive substrates include: a thermoplastic polymer substrate; a thermosetting polymer substrate; a cellulosic substrate, such as wood; leather; a textile substrate; a glass substrate; a ceramic substrate; and a composite material.

[0260] Regardless of the choice of the second re-bonding substrate (RB2), this substrate may be pre-treated prior to the contacting step. It is advisable to pre-treat the relevant surfaces to remove foreign matter therefrom, and any of the techniques described above for doing so may be used.

[0261] In order to ensure an effective fixing time, a primer composition consisting of a repair agent as defined above and an optional solvent and / or non-reactive diluent can be sandwiched between the first re-bonding substrate (RB1) and the second re-bonding substrate (RB2) by the above-mentioned contact step. To achieve this, it is envisaged that a layer of the primer composition can be applied to the residual adhesive disposed on the first re-bonding substrate (RB1). However, more conventionally, the optionally pre-treated second re-bonding substrate (RB2) can be treated with the primer composition before contacting with the first re-bonding substrate (RB1).

[0262] The primer composition can be applied to the relevant surface at a wet film thickness of 5-100 μm, for example 5-50 μm. In an alternative formulation of the present application which is not intended to be mutually exclusive with the formulation given above, the primer composition can be applied to the relevant surface at a wet film thickness of 0.01-10 g / m 2 , such as 0.1-2g / m 2 of coating weight applied.

[0263] The heat treatment of the residual cured adhesive composition should obviously be sufficient to activate the disulfide rearrangement in the residual adhesive. The heat treatment generally involves exposing the residual cured adhesive composition to a temperature in the range of 60° C. to 200° C., preferably 60° C. to 175° C., in particular 60° C. to 120° C. The appropriate temperature depends on the specific compounds present and can be determined in each case by a person skilled in the art using simple preliminary tests if necessary.

[0264] Attached Figure 3a to Figure 3c An exemplary embodiment of re-forming a bonded structure using the adhesive composition of the present invention is shown in : These figures depict the presence of residual cured adhesive composition (30) on the conductive first re-bonded substrate (31) obtained after the electrochemical debonding operation.

[0265] exist Figure 3a In an illustrative method of the present invention, a conductive second re-bonding substrate (32) which has itself been debonded is brought into contact with the residual adhesive layer (30) again. The second re-bonding substrate is shown here as having no residual adhesive thereon, which may be the result of a debonding operation or the result of a pre-treatment step to remove material from its surface. The contact of the first re-bonding substrate and the second re-bonding substrate (31, 32) sandwiches the previously cured adhesive therebetween. The resulting composite structure is then subjected to the above-described heat treatment conditions.

[0266] exist Figure 3b In an illustrative embodiment of the present invention, the second re-bonding substrate (34) is a new substrate, which means that it is not part of the initial composite structure that was debonded. The second re-bonding substrate (34) can have the same or different composition, physicochemical properties and structure as the conductive first re-bonding substrate (31). In addition, the second re-bonding substrate (34) is contacted with the conductive first re-bonding substrate (31) so that the residual adhesive layer (30) is sandwiched therebetween. The resulting composite structure is then subjected to the above-mentioned heat treatment conditions.

[0267] For the sake of completeness, it is not excluded that Figure 3b The second re-bonded substrate (34) is subjected to a pre-treatment step before being bonded to remove foreign matter therefrom as previously described.

[0268] exist Figure 3cIn an illustrative embodiment of the present invention, the second substrate (36) is also a new substrate, which means that it is not part of the initial composite structure that is debonded. In addition, the second re-bonding substrate (36) can also have the same or different composition, physicochemical properties and structure as the conductive first re-bonding substrate. However, in this embodiment, the optionally pre-treated second substrate (36) is primed with a layer (37) of a composition consisting of a repair agent and an optional solvent or non-reactive diluent. The optionally pre-treated, primed second re-bonding substrate (36) is contacted with the conductive first re-bonding substrate (31) so that the residual adhesive layer (30) is sandwiched therebetween, thereby ensuring that the adhesive layer contacts the applied primer layer. The resulting composite structure is then subjected to the above-mentioned heat treatment conditions.

[0269] The following examples illustrate the invention but are not intended to limit the scope of the invention in any way.

[0270] Example

[0271] The following materials were used in the examples:

[0272] DER 331: Bisphenol A epoxy resin available from Olin Corporation.

[0273] Thiocure 330: trimethylolpropane tris(3-mercaptopropionate), available from Bruno Bock.

[0274] Ajicure PN-H: curing catalyst available from Ajinmoto Fine Techno. Co. Ltd.

[0275] Bis(2-aminophenyl) disulfide: Curing agent (rebonding), available from Apollo Scientific Ltd.

[0276] 4-Aminophenyl disulfide: Curing agent (rebonding), available from Sigma Aldrich.

[0277] Cyphos IL169: tributyl(ethyl)phosphonium diethyl phosphate, available from Solvay.

[0278] EMIM MS: 1-ethyl-3-methylimidazolium methanesulfonate, available from Proionic.

[0279] Premix 182: A premix of epoxy resin (DER 331), fumed silica, and barbituric acid available from Henkel Corporation.

[0280] GPX 801: carbon black, available from Applied Nanostructured Solutions, LLC.

[0281] Omyacarb 4-HD: calcium carbonate filler available from Omya.

[0282] Luzenac 2: a lamellar talc filler available from Imerys.

[0283] Aerosil 202: Fumed silica post-treated with polydimethylsiloxane, available from Evonik Industries.

[0284] The following test methods have been used to characterize the formulations:

[0285] Initial bond strength, tensile lap shear (TLS) testing :The substrate tested is stainless steel (1.4301, thickness 1.5mm). The substrate is cut into 2.5cm×10cm plates for tensile testing. The bonding overlap area of ​​each plate is 2.5cm×1.0cm (1"×0.4"), wherein the bonding thickness is 150μm. For the initial bonding operation, the applied adhesive composition is cured at 100°C for 30 minutes in the overlapping area. Then, based on the determination of the tensile lap shear strength of EN 1465:2009 (German version) adhesive-bonded assemblies, a tensile lap shear (TLS) test is performed at room temperature. The test specimen is placed in the fixture of a universal testing machine and pulled at 10mm / min until failure occurs. The fixtures for fixing the ends of the assembly are aligned so that the applied force is applied through the center line of the specimen. The observed failure type can be adhesive (wherein the adhesive is separated from one of the substrates) or cohesive (wherein the adhesive breaks within itself).

[0286] Electrochemical debonding, tensile lap shear (TLS) testing (EN 1465:2009) : The test specimens were prepared according to the method described above, but before being placed in the universal testing machine, a constant potential (30 V) was applied across the overlapped bond area for a period of 20 minutes.

[0287] Re-bonding method : The samples obtained after electrochemical debonding were treated in one of the following three ways:

[0288] a) Method A: Figure 3a As depicted in , stainless steel plates (which had been used as test specimens in TLS tests after electrochemical debonding) were used to produce bonded assemblies again. The bond overlap area was likewise 2.5 cm×1.0 cm (1″×0.4″), with a bond thickness of 150 μm. The sandwiched adhesive was cured in the overlap area at 100° C. or 140° C. for 30 minutes, the temperatures used being recorded in the table below.

[0289] b) Method B: Figure 3b As depicted in , a new stainless steel plate (1.4301, 2.5 cm x 10 cm x 1.5 mm) was used to create the bonded assembly again. The bond overlap area was 2.5 cm x 1.0 cm (1" x 0.4") with a bond thickness of 150 μm. The sandwiched adhesive was cured in the overlap area at 100°C or 140°C for 30 minutes, the temperatures used being recorded in the table below.

[0290] c) Method C: Figure 3c As depicted in , new stainless steel plates (1.4301, 2.5 cm×10 cm×1.5 mm) were used to produce bonded assemblies again, wherein the surface of the plates had been primed with the repair agent present in the adhesive composition, i.e., 4-aminophenyl disulfide or bis(2-aminophenyl) disulfide (Table 1, Table 3). The repair agent was added at 0.2 g / cm 2 The amount of was applied in the overlap area. The bond overlap area was 2.5 cm x 1.0 cm (1" x 0.4") with a bond thickness of 150 μm. The sandwiched adhesive was cured in the overlap area at 100°C or 140°C for 30 minutes, the temperatures used are recorded in the table below.

[0291] According to the TLS test procedure above (EN 1465:2009), the bonded components obtained according to each of methods A to C are placed in the fixture of a universal testing machine and pulled at 10 mm / min until failure occurs. The fixtures used to fix the ends of the components are aligned so that the applied force is applied through the center line of the specimen. The observed failure type can be adhesive (where the adhesive separates from one of the substrates) or cohesive (where the adhesive breaks within itself).

[0292] Aging test :The substrate tested is aluminum (AA6016, thickness 1.25mm). The substrate is cut into 2.5cm×10cm plates for tensile testing. The bonding overlap area of ​​each substrate is 2.5cm×1.0cm, wherein the bonding thickness is 150μm. The applied adhesive composition is cured at 100°C for 30 minutes in the overlapping area. The specimens are stored in a climate chamber at 90% relative humidity and 65°C: at the specified time in storage (1 day, 7 days, 14 days and 21 days), a tensile lap shear (TLS) test is performed at room temperature according to the above method (EN1465:2009, German version). The test specimen is placed in the fixture of a universal testing machine and pulled at 10mm / min until failure occurs.

[0293] Example 1

[0294] A one-component composition having a molar ratio of epoxy reactive groups to epoxy groups of 0.8:1 was prepared according to Table 1 herein below. The given ingredients were mixed in a high-speed mixer (1200 rpm; 1 minute) to ensure a homogeneous mixture.

[0295] Table 1

[0296] Element Weight Percentage (wt%) DER 331 27.7 Thiocure 330 15.0 Ajicure PN-H 0.9 4-Aminophenyl disulfide 5.0 Cyphos IL 169 2.0 Omyacarb 4-HD 41.9 Luzenac 2 4.9 Aerosil R202 2.2 GPX 801 0.1 Premix 182 0.3

[0297] The tensile lap shear strength test was performed as described above. The results obtained are shown in Table 2 herein below.

[0298] Table 2

[0299]

[0300] It will be appreciated that the adhesive composition exhibits no detrimental degradation in bond strength when those bonded assemblies are exposed to high humidity and temperature conditions: this indicates the potential utility of the composition in consumer products and devices that need to be operable over a wide range of operating temperatures and other environmental conditions, including electronic devices in particular. The adhesive composition also exhibits effective electrochemical debonding under conditions of an applied potential of 30V for 20 minutes, and further exhibits at least 69% bond strength recovery in all rebonding methods used.

[0301] Example 2

[0302] A one-component composition having a molar ratio of epoxy-reactive groups to epoxy groups of 0.8:1 was prepared according to Table 3 herein below. The given ingredients were mixed in a high-speed mixer (1200 rpm; 1 minute) to ensure a homogeneous mixture.

[0303] Table 3

[0304]

[0305] The tensile lap shear strength test was performed as described above. The results obtained are shown in Table 4 herein below.

[0306] Table 4

[0307]

[0308] Composition 2A exhibited effective electrochemical debonding at an applied potential of 30 V for 20 minutes, and further exhibited at least 53% bond strength recovery in all rebonding methods used. Composition 2B exhibited a greater bond strength reduction at the applied potential, and also exhibited technically significant bond strength recovery using any of the rebonding methods.

[0309] Example 3

[0310] A one-component composition was prepared according to composition 2A of Table 3 herein above. As previously described, the given ingredients were mixed in a high-speed mixer (1200 rpm; 1 minute) to ensure a homogeneous mixture.

[0311] In an iterative manner, the tensile lap shear strength test was performed as described above. The results obtained are shown in Table 5 herein below.

[0312] Table 5

[0313]

[0314] In view of the foregoing description and examples, it will be apparent to those skilled in the art that equivalent modifications may be made without departing from the scope of the appended claims.

Claims

1. A curable and electrochemically debondable one-component (1K) adhesive composition comprising: a) at least one epoxy compound; b) a curing agent consisting of one or more compounds having at least one epoxy-reactive group and no disulfide functional groups; c) a healing agent consisting of one or more compounds containing at least one disulfide functional group and optionally at least one epoxy reactive group selected from hydroxyl, thiol, amine, or carboxyl; and d) electrolytes, The composition is characterized in that the molar ratio of epoxy-reactive groups to epoxy groups is from 0.6:1 to 1.2:

1.

2. The composition according to claim 1, wherein Based on the weight of the composition, the composition comprises: 15 to 50% by weight of a) at least one polyepoxide; 0.01 to 25% by weight of b) a curing agent consisting of one or more compounds having at least two epoxy-reactive groups and no disulfide functionality; 0.01 to 10% by weight of c) the repair agent; 0.5 to 15 wt % of d) the electrolyte; and 0 to 55% by weight of e) a rheology control agent, The composition is characterized in that the molar ratio of epoxy-reactive groups to epoxy groups is from 0.6:1 to 1.1:

1.

3. The composition according to claim 2, wherein Based on the weight of the composition, the composition comprises: 20 to 50% by weight, preferably 20 to 40% by weight, of a) at least one polyepoxide; 5 to 25 wt. %, preferably 5 to 20 wt. % of the curing agent, the curing agent consisting of one or more compounds having at least two epoxy-reactive groups and no disulfide functional groups; 1 to 10 wt %, preferably 2 to 8 wt % of c) the repair agent; 0.5 to 10 wt %, preferably 0.5 to 5 wt % of d) the electrolyte; and 1 to 55 wt. %, preferably 15 to 55 wt. % of e) the rheology control agent, The composition is characterized in that the molar ratio of epoxy-reactive groups to epoxy groups is from 0.75:1 to 0.95:

1.

4. The composition according to any one of claims 1 to 3, wherein the epoxy compound is selected from bisphenol A epoxy resin, bisphenol F epoxy resin, and mixtures thereof.

5. The composition according to any one of claims 1 to 4, wherein b) the curing agent comprises or consists of a thiol-functional compound selected from the group consisting of pentaerythritol tetrakisthioacetate (PETMP), tris(3-mercaptopropionate) (TMP), trimethylolpropane trimercaptoacetate (TMPMP), tris(2-(mercaptopropionyl)ethyl)isocyanate, ethylene glycol dimercaptoacetate, and mixtures thereof.

6. The composition of any one of claims 1-5, wherein the repair agent comprises a compound selected from the group consisting of: bis(4-aminophenyl) disulfide; bis(2-aminophenyl) disulfide; 2-amino-4-chlorophenyl disulfide; and mixtures thereof.

7. A composition according to any one of claims 1 to 5, wherein the repair agent comprises a compound selected from the group consisting of: 3,3'-dithiopropionic acid; 4,4'-dithiobutyric acid; bis(10-carboxydecyl) disulfide; 2,2'-dithiobisethylamine (cystamine); (2R)-2-amino-3-[[(2R)-2-amino-2-carboxyethyl]disulfanyl]propionic acid (L-cystine); and mixtures thereof.

8. The composition of any one of claims 1-5, wherein the healing agent comprises a liquid thiol-terminated polysulfide polymer.

9. The composition according to any one of claims 1 to 8, wherein the electrolyte is selected from: 1-ethyl-3-methyl-1H-imidazol-3-ium methane sulfonate; 1-ethyl-3-methyl-1H-imidazol-3-ium methyl sulfate; 1-methylimidazolium bis(trifluoromethylsulfonyl)imide; 3-methylimidazolium bis(trifluoromethylsulfonyl)imide; 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide; 1-propyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide; 1-butyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide; 1-butyl-2,3-dimethylimidazolium bis(trifluoromethylsulfonyl)imide; 1-hexyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide ; 1-octyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide; 1-methyl-3-octylimidazolium bis(trifluoromethylsulfonyl)imide; 1-decyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide; 1-dodecyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide; tetraethylphosphonium bis(trifluoromethylsulfonyl)imide; tetrabutylphosphonium Phosphonium bis(trifluoromethylsulfonyl)imide; tetraoctylphosphonium bis(trifluoromethylsulfonyl)imide; trihexyl(tetradecyl)phosphonium bis(trifluoromethylsulfonyl)imide; tridecyl(tetradecyl)phosphonium bis(trifluoromethylsulfonyl)imide; tributyl(methyl)phosphonium diethyl phosphate; tributyl(ethyl)phosphonium diethyl phosphate; tetraoctylphosphonium diethyl phosphate; and mixtures thereof.

10. The composition of claim 9, wherein the electrolyte is selected from: 1-ethyl-3-methyl-1H-imidazol-3-ium methane sulfonate; 1-ethyl-3-methyl-1H-imidazol-3-ium methyl sulfate; trihexyl(tetradecyl)phosphonium bis(trifluoromethylsulfonyl)imide; tributyl(methyl)phosphonium diethyl phosphate; tributyl(ethyl)phosphonium diethyl phosphate; and mixtures thereof.

11. The composition of any one of claims 2-10, wherein the rheology control agent comprises a non-conductive filler selected from the group consisting of: calcium carbonate; calcium oxide; calcium metasilicate; fumed silica; silicon dioxide; talc; barium sulfate; and mixtures thereof.

12. A bonded structure comprising: a first substrate having a conductive surface; as well as a second substrate having a conductive surface; The cured adhesive composition according to any one of claims 1 to 11 is disposed between the first substrate and the second substrate.

13. A method of debonding a bonded structure as defined in claim 12, said method comprising the steps of: i) applying a voltage across the two surfaces to form an anodic interface and a cathodic interface; as well as ii) debonding the surface.

14. The method according to claim 13, wherein the voltage applied in step i) is 0.5-100 V and is preferably applied for a duration of 1 second to 60 minutes.

15. A method of treating a bonded structure as defined in claim 12, said method comprising the steps of: i) applying a voltage across the two surfaces to form an anodic interface and a cathodic interface; as well as ii) debonding the surface to provide a first substrate having the cured adhesive composition disposed on the conductive surface of the first substrate; iii) contacting the first substrate with a third substrate so that the cured adhesive composition is sandwiched between the first substrate and the third substrate; as well as iv) heat treating the residual cured adhesive composition to bond the first substrate and the third substrate together.

Citation Information

Patent Citations

  • Preparation of carbonates

    EP0119840A1

  • A curable composition

    EP0520426B1

  • Latent hardener and stable heat cured epoxy compositions

    GB1121196A

  • Production of alkylene carbonates

    GB1485925A

  • Primer composition for anaerobic adhesive

    GB2502554A